Laminated body, method for manufacturing laminated body, and virtual reality display device
By using a laminated body of an alignment film with a film thickness of 10% or less and a light absorption anisotropic layer in a virtual reality display device, the problems of virtual image distortion and poor durability caused by poor light reflection are solved, and better display performance and durability are achieved.
Patent Information
- Application Number
- CN202380060671.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-23
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-01
AI Technical Summary
In the existing virtual reality display devices, the poor reflection of light causes virtual image distortion, poor display performance, and when using an absorption linear polarizer, the durability of the light absorption anisotropic layer is poor.
The laminated body having an orientation film that satisfies the variation of the predetermined film thickness and a light-absorbing anisotropic layer are used, and the display performance is improved by introducing the laminated body into a virtual reality display device.
By using an alignment film whose film thickness changes to 10% or less, adverse reflection of light rays is suppressed, distortion of virtual images is reduced, display performance is improved, and durability of the light-absorbing anisotropic layer is enhanced.
Smart Images

Figure CN119744360A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a laminate, a method for manufacturing the laminate and a virtual reality display device. Background Art
[0002] In recent years, virtual reality display devices have been known as display devices that enable a user to obtain a sense of presence as if entering a virtual world by wearing dedicated headphones on the head and visually recognizing images displayed through lenses.
[0003] Such virtual reality display devices generally include an image display panel and a Fresnel lens. However, since the distance from the image display panel to the Fresnel lens increases, it is known that there is a problem that the headset becomes thicker and the wearability is poor.
[0004] In view of the above problems, Patent Document 1 describes a lens structure called a cookie lens, which has an image display panel, a reflective polarizer and a half-reflective mirror. The overall thickness of the headset is thinned by allowing the light emitted from the image display panel to travel back and forth between the reflective polarizer and the half-reflective mirror.
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2020-519964 Summary of the invention
[0008] Technical issues to be solved by the invention
[0009] The present inventors have found out that the virtual reality display device described in Patent Document 1 etc. has the following problem: depending on the optical components used, part of the light emitted from the image display panel is distorted due to poor reflection, and the image is magnified and visually recognized as a distorted image, resulting in poor display performance.
[0010] Furthermore, the present inventors have clarified that when an absorptive linear polarizer is introduced into a virtual reality display device, when a light-absorbing anisotropic layer containing a liquid crystal compound and a dichroic substance is used as the absorptive linear polarizer, if at least one surface of the light-absorbing anisotropic layer is disposed adjacent to an adhesive layer, a problem of poor durability arises, and therefore it is necessary to introduce the light-absorbing anisotropic layer in a state of being stacked with other layers (for example, an oriented film) (a stack).
[0011] Therefore, an object of the present invention is to provide a laminate, a method for producing the laminate, and a virtual reality display device, which can improve the display performance of the virtual reality display device when the laminate including the light absorption anisotropic layer is introduced into the virtual reality display device.
[0012] Means for solving technical problems
[0013] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that if a laminate having an oriented film and a light absorption anisotropic layer satisfying a predetermined film thickness variation is introduced into a virtual reality display device, the display performance of the virtual reality display device can be improved, thereby completing the present invention.
[0014] That is, the present inventors have found that the above-mentioned problems can be solved by the following configuration.
[0015] [1] A laminate comprising an alignment film and a light-absorbing anisotropic layer provided on the alignment film, wherein:
[0016] The light absorption anisotropic layer contains a liquid crystal compound and a dichroic substance.
[0017] The variation in the film thickness of the alignment film was 10% or less.
[0018] [2] The laminate according to [1], wherein
[0019] The dichroic substance contains a dichroic azo dye compound having a thienothiazole skeleton.
[0020] [3] The laminate according to [1] or [2], wherein
[0021] The content of the dichroic substance contained in the light absorption anisotropic layer is 40 to 250 mg / cm 3 .
[0022] [4] The laminate according to any one of [1] to [3], wherein
[0023] The oriented film contains a polymer compound.
[0024] When the secondary ion intensity derived from the polymer compound in the oriented film is measured using time-of-flight secondary ion mass spectrometry while irradiating an ion beam from the surface of the light absorbing anisotropic layer side of the oriented film toward the surface on the opposite side of the light absorbing anisotropic layer, the maximum value of the secondary ion intensity derived from the polymer compound exists in the region from the surface on the opposite side of the light absorbing anisotropic layer to the thickness position of 100 nm.
[0025] [5] The laminate according to [4], wherein
[0026] The polymer compound has a repeating unit represented by the formula (2) described later.
[0027] [6] The laminate according to any one of [1] to [5], wherein
[0028] A protective layer is provided on the side of the light absorption anisotropic layer opposite to the alignment film.
[0029] The oxygen permeability coefficient of the protective layer is 200cc / m 2 ·day·atm or less.
[0030] [7] The laminate according to [6], wherein
[0031] The protective layer is composed of a polyvinyl alcohol-based resin film.
[0032] [8] The laminate according to any one of [1] to [5], which comprises an alignment film, a light absorption anisotropic layer, a tackiness adhesive layer, and a retardation layer adjacent to each other in this order.
[0033] [9] The laminate according to [8], wherein
[0034] The oxygen coefficient of the adhesive layer is 200cc / m 2 ·day·atm or less.
[0035]
[10] The laminated body according to any one of [1] to [9], which has a curved shape.
[0036]
[11] A method for producing a laminated body, which is a method for producing a laminated body according to any one of [1] to
[10] , the method comprising:
[0037] an alignment film forming step of forming an alignment film on a substrate using an alignment film forming composition;
[0038] a light absorption anisotropic layer forming step of forming a light absorption anisotropic layer on the alignment film using a light absorption anisotropic layer forming composition containing a liquid crystal compound and a dichroic substance after the alignment film forming step; and
[0039] The substrate peeling step is to peel off the substrate after the light absorption anisotropic layer forming step to produce a laminate of the alignment film and the light absorption anisotropic layer.
[0040]
[12] The method for producing a laminate according to
[11] , wherein:
[0041] The composition for forming an alignment film contains a polymer compound.
[0042] The absolute value of the difference between the SP value of the polymer compound and the SP value of the substrate is 1.7 MPa1 / 2 the following.
[0043]
[13] The method for producing a laminate according to
[11] or
[12] , wherein:
[0044] The viscosity of the alignment film forming composition at 25° C. is 2 mPa·s or more and less than 10 mPa·s.
[0045]
[14] The method for producing a laminate according to any one of
[11] to
[13] , wherein
[0046] The alignment film forming step includes a drying process of drying the coating film to a solid content concentration of 60% or less by wind at a wind speed of 2 m or less after applying the alignment film forming composition on the substrate.
[0047]
[15] A virtual reality display device, comprising, in order, an image display panel, a first absorbing linear polarizer, a first phase difference layer, a reflecting circular polarizer, a half mirror, a second phase difference layer and a second absorbing linear polarizer,
[0048] The second absorbing linear polarizer is the laminate according to any one of claims 1 to 10.
[0049] Effects of the Invention
[0050] According to the present invention, it is possible to provide a laminate, a method for producing the laminate, and a virtual reality display device that can improve the display performance of the virtual reality display device when the laminate including the light absorption anisotropic layer is introduced into the virtual reality display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a conceptual diagram for explaining the variation in the film thickness of the alignment film.
[0052] Figure 2 This is a schematic cross-sectional view showing an example of the virtual reality display device of the present invention. DETAILED DESCRIPTION
[0053] Hereinafter, the present invention will be described in detail.
[0054] The description of the constituent elements described below is based on typical embodiments of the present invention, but the present invention is not limited to these embodiments.
[0055] In addition, in this specification, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0056] In addition, in this specification, regarding each component, one substance corresponding to each component can be used alone, or two or more substances can be used simultaneously. Here, regarding each component, when two or more substances are used simultaneously, unless otherwise specified, the content of the component refers to the total content of the substances used simultaneously.
[0057] In addition, in this specification, "(meth)acrylic acid" is a mark which represents "acrylic acid" or "methacrylic acid".
[0058] In this specification, Re(λ) and Rth(λ) represent the in-plane retardation and the retardation in the thickness direction at a wavelength λ, respectively. In addition, unless otherwise specified, the wavelength λ is set to 550 nm.
[0059] In this specification, Re(λ) and Rth(λ) are values measured at a wavelength λ using AxoScan (manufactured by Axometrics).
[0060] Specifically, by inputting the average refractive index ((nx+ny+nz) / 3) and film thickness (d(μm)) into AxoScan, we can calculate:
[0061] In-plane slow axis direction (°);
[0062] Re(λ)=R0(λ);
[0063] Rth(λ)=((nx+ny) / 2-nz)×d.
[0064] In addition, RO(λ) is displayed as a numerical value calculated by AxoScan, but it means Re(λ).
[0065] [Laminated body]
[0066] The laminate of the present invention is a laminate having an alignment film and a light absorption anisotropic layer provided on the alignment film.
[0067] Furthermore, the light absorption anisotropic layer included in the laminate of the present invention contains a liquid crystal compound and a dichroic substance.
[0068] Furthermore, the thickness variation of the oriented film included in the laminate of the present invention is 10% or less.
[0069] Here, the coefficient of variation of the alignment film refers to a value calculated by the following procedure.
[0070] First, for a laminate including an oriented film (e.g., a laminate having a substrate, an oriented film, and a light absorbing anisotropic layer, etc.), an interference film thickness measuring device (e.g., FE3000 manufactured by Otsuka Electronics Co., Ltd., etc.) is used to measure the reflectivity with a lens magnification of 25 times. In addition, for the measurement, 101 points are measured at a distance of 10 cm at a spacing of 1 mm. And, in the case where the measured object is a curved surface shape or the sample size is less than 10 cm, for the measurement, when the straight line is overlapped on the object, the straight line with the longest distance between the intersection of the object and the straight line is selected, and the straight line is divided into 100 equal parts, and the thickness of each point is measured.
[0071] Next, for each layer of the laminate including the oriented film, the refractive index at a wavelength of 400 nm to 800 nm was calculated by the base analysis method, and the calculated refractive index was used to fit the wavelength of 400 nm to 800 nm by the FFT (Fast Fourier Transform) method to calculate the film thickness. In addition, the unit of the film thickness is [nm].
[0072] Next, regarding the graph of the film thickness of the alignment film obtained by fitting (for example, Figure 1 ), the area with a film thickness thicker than the average film thickness (average value) is set as a peak, and the area with a film thickness thinner than the average thickness (average value) is set as a valley peak, the maximum value of the peak is set as the peak thickness and the minimum value of the valley peak is set as the valley peak thickness, and the difference between the adjacent peak thickness and the valley peak thickness is defined as the film thickness variation reference value of each element. The film thickness variation of all adjacent elements is calculated, and the maximum value thereof is calculated as the film thickness variation reference value of the alignment film.
[0073] In addition, when it is difficult to measure with an interference film thickness measuring device, the thickness can also be measured by morphological observation based on a scanning electron microscope (SEM). At this time, the stacked body including the light absorption anisotropic layer is cut with a slicer to expose the cross section, and the cross section is observed by SEM at an appropriate magnification (20,000 to 50,000 times) to obtain the film thickness of the light absorption anisotropic layer. In addition, for ease of observation, the sample can be subjected to appropriate treatments such as carbon evaporation and etching. The acceleration voltage is optimized under conditions of 1kV to 10kV. In addition, the stacked body can be peeled off from a substrate such as a lens, or the cross section can be cut including the substrate. Regarding the measurement position, when observing the stacked body from above, it is divided into 10 equal parts on a straight line passing through the center of gravity of the surface and 9 points other than the end are measured. In the same way as above, the average film thickness of the oriented film and the film thickness variation reference value of the oriented film are calculated.
[0074] Next, the calculated film thickness variation reference value of the alignment film is used to calculate the film thickness variation of the alignment film according to the following formula.
[0075] Alignment film thickness variation (%) = (alignment film thickness variation reference value) ÷ (alignment film average thickness)
[0076] When the thickness can be measured by both the interference film thickness measuring device and the morphological observation by SEM, the film thickness variation value is determined based on the measurement result by the interference film thickness measuring device.
[0077] As described above, when the laminate of the present invention including an alignment film and a light absorption anisotropic layer with a thickness variation of 10% or less is introduced into a virtual reality display device, the display performance of the virtual reality display device can be improved.
[0078] This is believed to be because, by using an alignment film with a thickness variation of less than 10%, undesirable reflections caused by a portion of the light emitted from the display panel are suppressed, thereby suppressing the distortion of the virtual image. In addition, among the multiple optical components used in the virtual reality display device, the alignment film is focused on, and the effect of improving the display performance by setting the thickness variation of the alignment film to less than 10% can be said to be a significant effect (unpredictable effect).
[0079] Hereinafter, the alignment film and the light absorption anisotropic layer included in the laminate of the present invention will be described.
[0080] 〔Oriented film〕
[0081] As described above, the alignment film included in the laminate of the present invention has a thickness variation of 10% or less, preferably an alignment film having a thickness variation of more than 0% and less than 6%, and more preferably an alignment film having a thickness variation of more than 0% and less than 3%.
[0082] The oriented film of the laminate of the present invention is not particularly limited except that the variation in film thickness is 10% or less, and may be a rubbed oriented film formed by rubbing treatment or a photo-oriented film formed by light irradiation, as long as the light absorption anisotropic layer described later can be set to a desired oriented state. Among them, the photo-oriented film is preferred.
[0083] <Photo-alignment film>
[0084] As a photo-alignment compound for a photo-alignment film formed by light irradiation, it is described in many documents, etc. In the present invention, as a preferred example, for example, the azo compounds described in Japanese Patent Publication No. 2006-285197, Japanese Patent Publication No. 2007-76839, Japanese Patent Publication No. 2007-138138, Japanese Patent Publication No. 2007-94071, Japanese Patent Publication No. 2007-121721, Japanese Patent Publication No. 2007-140465, Japanese Patent Publication No. 2007-156439, Japanese Patent Publication No. 2007-133184, Japanese Patent Publication No. 2009-109831, Japanese Patent No. 3883848, and Japanese Patent No. 4151746 can be cited. Compounds; aromatic ester compounds described in Japanese Patent Publication No. 2002-229039; maleimide and / or alkenyl-substituted naphthalene diimide compounds having photo-alignment units described in Japanese Patent Publication No. 2002-265541 and Japanese Patent Publication No. 2002-317013; photo-crosslinkable silane derivatives described in Japanese Patent No. 4205195 and Japanese Patent No. 4205198; and photo-crosslinkable polyimide, polyamide or ester described in Japanese Patent Table No. 2003-520878, Japanese Patent Table No. 2004-529220 or Japanese Patent No. 4162850. More preferably, azo compounds, photo-crosslinkable polyimide, polyamide or ester.
[0085] Among these, it is preferable to use, as the photo-alignment compound, a photosensitive compound having a photo-alignment group that undergoes at least one of dimerization and isomerization by the action of light.
[0086] In addition, as the photo-alignment group, for example, there can be mentioned a group having a cinnamic acid (cinnamoyl) structure (skeleton), a group having a coumarin structure (skeleton), a group having a chalcone structure (skeleton), a group having a benzophenone structure (skeleton), and a group having an anthracene structure (skeleton). Among these groups, a group having a cinnamoyl structure and a group having a coumarin structure are preferred, and a group having a cinnamoyl structure is more preferred.
[0087] Furthermore, the photosensitive compound having the above-mentioned photo-alignment group may further have a crosslinking group.
[0088] The crosslinkable group is preferably a thermal crosslinkable group that causes a curing reaction by heat or a photo crosslinkable group that causes a curing reaction by light, and may be a crosslinkable group having either a thermal crosslinkable group or a photo crosslinkable group.
[0089] As the crosslinkable group, for example, at least one selected from the group consisting of an epoxy group, an oxetane group, a group represented by -NH-CH2-OR (R represents a hydrogen atom or an alkyl group having 1 to 20 carbon atoms), a group having an ethylenically unsaturated double bond, and a blocked isocyanate group can be cited. Among them, an epoxy group, an oxetane group, and a group having an ethylenically unsaturated double bond are preferred.
[0090] In addition, a three-membered ring cyclic ether group is also called an epoxy group, and a four-membered ring cyclic ether group is also called an oxetanyl group.
[0091] Furthermore, specific examples of the group having an ethylenically unsaturated double bond include a vinyl group, an allyl group, a styryl group, an acryloyl group, and a methacryloyl group, and an acryloyl group or a methacryloyl group is preferred.
[0092] The photo-alignment film formed of the above-mentioned material is irradiated with linearly polarized light or non-polarized light to produce the photo-alignment film.
[0093] In this specification, "linearly polarized light irradiation" and "non-polarized light irradiation" are operations for causing a photoreaction in a photo-alignment material. The wavelength of the light used varies depending on the photo-alignment material used, and is not particularly limited as long as it is a wavelength required for the photoreaction. The peak wavelength of the light used for light irradiation is preferably 200nm to 700nm, and more preferably ultraviolet light with a peak wavelength of 400nm or less.
[0094] The light source used for light irradiation includes commonly used light sources, such as tungsten lamps, halogen lamps, xenon lamps, xenon flash lamps, mercury lamps, mercury-xenon lamps and carbon arc lamps, various lasers [for example, semiconductor lasers, helium-neon lasers, argon ion lasers, helium-cadmium lasers and YAG (yttrium aluminum garnet) lasers], light emitting diodes and cathode ray tubes, etc.
[0095] As a method of obtaining linearly polarized light, a method using a polarizing plate (e.g., an iodine polarizing plate, a dichroic dye polarizing plate, and a wire grid polarizing plate), a method using a prism element (e.g., a Glan-Thomson prism) or a reflective polarizer using the Brewster angle, or a method using light emitted from a laser light source having polarized light can be adopted. In addition, a filter or a wavelength conversion element can be used to selectively irradiate only light of a desired wavelength.
[0096] When the irradiated light is linearly polarized light, the method of irradiating the alignment film with light from the top or back, perpendicularly or obliquely to the alignment film surface can be adopted. The incident angle of light varies depending on the photo-alignment material, but is preferably 0 to 90° (perpendicular), preferably 40 to 90°.
[0097] In the case of non-polarized light, the alignment film is irradiated with non-polarized light from an oblique direction, and the incident angle is preferably 10 to 80°, more preferably 20 to 60°, and further preferably 30 to 50°.
[0098] The irradiation time is preferably 1 minute to 60 minutes, more preferably 1 minute to 10 minutes.
[0099] When patterning is required, a method of performing light irradiation using a photomask a number of times required for patterning, or a method of writing a pattern by laser scanning can be adopted.
[0100] In the present invention, the alignment film is preferably a photo-alignment film formed using an alignment film-forming composition containing a photo-alignment compound (particularly, a photosensitive compound having a photo-alignment group).
[0101] Furthermore, in the present invention, it is preferred to contain a polymerization initiator from the viewpoint of freely controlling the releasability of the alignment film-forming composition from any member (eg, substrate) provided on the side opposite to the light-absorbing anisotropic layer of the alignment film.
[0102] The polymerization initiator is not particularly limited, and examples thereof include photoradical polymerization initiators and thermal cationic polymerization initiators, depending on the form of the polymerization reaction.
[0103] As the polymerization initiator, a photoradical polymerization initiator capable of initiating a polymerization reaction by ultraviolet irradiation is preferred.
[0104] Examples of the photoradical polymerization initiator include α-carbonyl compounds, acyloin ethers, α-hydrocarbon-substituted aromatic acyloin compounds, polynuclear quinone compounds, a combination of a triaryl imidazole dimer and p-aminophenyl ketone, acridine and phenazine compounds, oxadiazole compounds, and acylphosphine oxide compounds.
[0105] When the alignment film forming composition contains a photoradical polymerization initiator, the content of the photoradical polymerization initiator is preferably 0.1 to 10% by mass, more preferably 1 to 5% by mass, based on the total solid content of the alignment film forming composition.
[0106] When the alignment film forming composition contains a thermal cationic polymerization initiator, the content of the thermal cationic polymerization initiator is preferably 1 to 30% by mass, more preferably 4 to 20% by mass, based on the total solid content of the alignment film forming composition.
[0107] Furthermore, in the present invention, the alignment film-forming composition preferably contains a solvent.
[0108] Examples of the solvent include ketones (e.g., acetone, 2-butanone, methyl isobutyl ketone, cyclopentanone, and cyclohexanone), ethers (e.g., dioxane and tetrahydrofuran), aliphatic hydrocarbons (e.g., hexane), alicyclic hydrocarbons (e.g., cyclohexane), aromatic hydrocarbons (e.g., toluene, xylene, and trimethylbenzene), halogenated carbons (e.g., dichloromethane, dichloroethylene, dichlorobenzene, and chlorotoluene), esters (e.g., methyl acetate, ethyl acetate, and butyl acetate), water, alcohols (e.g., ethanol, isopropanol, butanol, and cyclohexanol), cellosolves (e.g., methyl cellosolve and ethyl cellosolve), cellosolve acetates, sulfoxides (e.g., dimethyl sulfoxide), and amides (e.g., dimethylformamide and dimethylacetamide).
[0109] The solvent may be used alone or in combination of two or more.
[0110] <Polymer Compounds>
[0111] In the present invention, since the peeling property of any component (for example, a substrate) provided on the side opposite to the light absorbing anisotropic layer of the above-mentioned alignment film becomes good, it is preferred that the above-mentioned alignment film contains a polymer compound, and when the secondary ion intensity derived from the polymer compound in the alignment film is measured using time-of-flight secondary ion mass spectrometry (TOF-SIMS) while irradiating an ion beam from the surface on the light absorbing anisotropic layer side of the above-mentioned alignment film toward the surface on the side opposite to the light absorbing anisotropic layer, the maximum value of the secondary ion intensity derived from the polymer compound exists in the region from the surface on the side opposite to the light absorbing anisotropic layer to a thickness position of 100 nm.
[0112] Here, when the alignment film contains two or more polymer compounds, at least one polymer compound may be concentrated on the side opposite to the light absorption anisotropic layer.
[0113] In the following description, the maximum value of the secondary ion intensity derived from the polymer compound existing in the region from the surface on the opposite side of the light absorption anisotropic layer to the thickness position of 100 nm is also simply referred to as "the polymer compound is concentrated on the opposite side of the light absorption anisotropic layer".
[0114] Furthermore, as a method for confirming that the polymer compound is concentrated on the side opposite to the light absorption anisotropic layer, a method of evaluating the position where the secondary ion intensity derived from the polymer compound shows a maximum value using TOF-SIMS can be cited. Specifically, when analyzing the components in the depth direction of the stacked body by TOF-SIMS while irradiating an ion beam, a series of operations of repeatedly performing component analysis of a surface depth region of 1 to 2 nm, further digging 1 nm to several hundred nm along the depth direction, and performing component analysis of the next surface depth region of 1 to 2 nm can be confirmed based on the position where the ion intensity shows a maximum value.
[0115] In the present invention, the polymer compound preferably has a repeating unit represented by formula (2) described below because the releasability from any member (eg, substrate) provided on the side opposite to the light absorption anisotropic layer of the alignment film becomes good.
[0116] Furthermore, as the above-mentioned polymer compound, from the viewpoint of being able to freely control the peeling property of any component (for example, a substrate) arranged on the side opposite to the light-absorbing anisotropic layer of the above-mentioned orientation film, it is preferably at least one specific compound selected from the group including polymerizable polymers having polymerizable groups on side chains and polymers of the above-mentioned polymerizable polymers.
[0117] (Specific Compound)
[0118] Regarding the polymerizable macromolecule which is one embodiment of the specific compound, the polymerizable group on the side chain is not particularly limited, but is preferably a polymerizable group capable of radical polymerization or cation polymerization.
[0119] Here, as a radical polymerizable group (photo-crosslinkable group), a (meth)acryloyl group, an acrylamide group, a vinyl group, a styryl group, an allyl group, etc. are mentioned, for example.
[0120] Examples of the cationically polymerizable group (thermal crosslinkable group) include a vinyl ether group, an oxirane group, and an oxetane group.
[0121] In the present invention, the polymerizable group is preferably a (meth)acryloyl group from the viewpoint of easily controlling the releasability from any member (eg, substrate) provided on the side opposite to the light absorption anisotropic layer of the alignment film.
[0122] Furthermore, in the present invention, the polymerizable polymer preferably does not have the photo-alignment group described above in the photo-alignment compound.
[0123] The structure of the main chain of the above-mentioned polymerizable polymer is not particularly limited, and known structures can be cited, for example, it is preferably a skeleton selected from the group including a (meth)acrylic skeleton, a styrene skeleton, a siloxane skeleton, a cycloolefin skeleton, a methylpentene skeleton, an amide skeleton and an aromatic ester skeleton.
[0124] Among these, a skeleton selected from the group consisting of a (meth)acrylic skeleton, a siloxane skeleton, and a cycloolefin skeleton is more preferred, and a (meth)acrylic skeleton is further preferred.
[0125] In the present invention, the polymerizable polymer preferably has a repeating unit represented by the following formula (1) because the releasability from any member (eg, substrate) provided on the side opposite to the light absorption anisotropic layer of the alignment film becomes better.
[0126] [Chemical formula 1]
[0127]
[0128] R 1 It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0129] L 1 represents a single bond or an n+1 valent linking group. For example, when n is 1, L 1 represents a divalent linking group. When n is 2, L 1 represents a trivalent linking group. 1 In the case of a single bond, n represents 1.
[0130] As the divalent linking group, as the divalent linking group, there can be mentioned a divalent aliphatic hydrocarbon group (for example, an alkylene group) which may have a substituent, an arylene group which may have a substituent, a heteroarylene group which may have a substituent, -O-, -CO-, -NH-, or a group formed by combining two or more of these. As the above-mentioned group formed by combining two or more of these, there can be mentioned a divalent aliphatic hydrocarbon group which may have a -CO-O- substituent, a divalent aliphatic hydrocarbon group which may have -O-, -CO-O- substituents, a divalent aliphatic hydrocarbon group which may have -NH- and -CO-O- substituents, and a divalent aliphatic hydrocarbon group which may have a -O-CO-NH substituent.
[0131] Examples of the trivalent linking group include a trivalent aliphatic hydrocarbon group which may have a substituent, a trivalent aromatic group which may have a substituent, a nitrogen atom (>N-), and a group formed by combining these groups with the above-mentioned divalent linking group.
[0132] P 1represents a polymerizable group. Examples of the polymerizable group include polymerizable groups capable of the above-mentioned radical polymerization or cationic polymerization.
[0133] n represents an integer greater than 1. However, n is preferably 1 or 2, and more preferably 1, because the peeling property from any member (for example, substrate) provided on the opposite side of the alignment film from the light absorption anisotropic layer becomes better.
[0134] The content of the repeating unit represented by the above formula (1) is preferably 20% by mass or more, more preferably 30% by mass or more, and further preferably 50% by mass or more relative to the total mass of all repeating units of the polymerizable polymer. The upper limit is not particularly limited, but 100% by mass and 95% by mass or less are more common.
[0135] Examples of the repeating unit represented by the formula (1) include the repeating units shown in Table 1 below. These may be used alone or in combination of two or more.
[0136] [Table 1]
[0137]
[0138] The polymerizable polymer may have other repeating units in addition to the repeating unit represented by the above formula (1).
[0139] As other repeating units, a repeating unit represented by the following formula (2) can be cited because the peeling property from any member (for example, substrate) provided on the opposite side of the alignment film to the light absorption anisotropic layer becomes better.
[0140] [Chemical formula 2]
[0141]
[0142] R 2 It represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0143] L 2 represents a single bond or a divalent linking group. Examples of the divalent linking group include L 1 The groups exemplified as the divalent linking groups represented by .
[0144] R 3 It represents an aliphatic hydrocarbon group which may have a substituent, or a group in which one or more -CH2- constituting the aliphatic hydrocarbon group is substituted with -O-, -S-, -NH-, -N(Q)- or -CO-. Q represents a substituent.
[0145] The number of carbon atoms contained in the aliphatic hydrocarbon group is not particularly limited, but is preferably 1-20, more preferably 1-10.
[0146] The aliphatic hydrocarbon group may be linear or branched, and may have a cyclic structure.
[0147] The substituent is not particularly limited, and examples thereof include alkyl, alkoxy, alkyl-substituted alkoxy, cyclic alkyl, aryl (eg, phenyl and naphthyl), cyano, amino, nitro, alkylcarbonyl, sulfo, and hydroxyl.
[0148] When the polymerizable polymer contains other repeating units, the content of the other repeating units (for example, the repeating units represented by the above formula (2)) is not particularly limited, but is preferably 80% by mass or less, more preferably 50% by mass or less, and further preferably 30% by mass or less relative to the total mass of all repeating units of the polymerizable polymer. The lower limit is not particularly limited, but can be 5% by mass or more.
[0149] Examples of other repeating units include the repeating units shown in Table 2 below. These may be used alone or in combination of two or more.
[0150] [Table 2]
[0151]
[0152] In the present invention, the weight average molecular weight of the above-mentioned polymer compound is preferably 5000 to 100000, and more preferably 7500 to 50000, for the reason that the peeling property from any component (for example, a substrate) provided on the side opposite to the light absorption anisotropic layer of the above-mentioned oriented film becomes better and the solubility in the coating liquid is ensured.
[0153] Here, the weight average molecular weight is a value measured by gel permeation chromatography (GPC) under the conditions shown below.
[0154] Solvent (eluent): THF (tetrahydrofuran)
[0155] Device name: TOSOH HLC-8320GPC
[0156] Column: 3 TOSOH TSKgel Super HZM-H (4.6 mm x 15 cm) connected and used
[0157] Column temperature: 40℃
[0158] Sample concentration: 0.1 mass%
[0159] Flow rate: 1.0ml / min
[0160] Calibration curve: Calibration curve of seven samples with Mw=2800000 to 1050 (Mw / Mn=1.03 to 1.06) using TSK standard polystyrene manufactured by TOSOH
[0161] In the present invention, the polymer compound is preferably a polymer of the polymerizable polymer in the specific compound, that is, a cross-linked body of the polymerizable polymer, because the peeling property of any component (for example, a substrate) arranged on the side opposite to the light-absorbing anisotropic layer of the orientation film becomes better.
[0162] In the present invention, the content of the polymer compound is preferably 0.2 to 20 mass %, more preferably 0.3 to 10 mass %, and even more preferably 0.4 to 8 mass % based on the mass of the alignment film because the degree of orientation of the light absorption anisotropic layer described later becomes high.
[0163] <Surfactant>
[0164] In the present invention, when the laminate of the present invention is introduced into a virtual reality display device, the alignment film (particularly the photo-alignment film) preferably contains a surfactant because the display performance of the virtual reality display device can be further improved.
[0165] By containing a surfactant, it is expected that the smoothness of the coating surface is improved to further improve the degree of orientation, or that depressions and unevenness are suppressed to improve the uniformity within the surface.
[0166] In particular, from the reason of suppressing depression when forming a light absorption anisotropic layer on the oriented film, as a surfactant, a polymer having a repeating unit B described in paragraphs
[0037] to
[0053] of International Publication No. 2022 / 024683 (hereinafter referred to as "acid-cleavable surfactant") can be preferably used.
[0167] The thickness of the alignment film is not particularly limited, but is preferably 0.1 to 10 μm, and more preferably 0.5 to 5 μm.
[0168] 〔Light absorption anisotropic layer〕
[0169] The light absorption anisotropic layer included in the laminate of the present invention is a layer containing a liquid crystal compound and a dichroic substance and provided on the above-mentioned alignment film, and is preferably a layer in which the alignment state of the liquid crystal compound and the dichroic substance is fixed.
[0170] Hereinafter, the liquid crystal compound, the dichroic substance, and the optional components contained in the light absorption anisotropic layer will be described.
[0171] <Liquid Crystalline Compound>
[0172] As the liquid crystal compound, any of a high molecular weight liquid crystal compound and a low molecular weight liquid crystal compound can be used.
[0173] Here, the "polymer liquid crystal compound" refers to a liquid crystal compound having a repeating unit in its chemical structure.
[0174] Furthermore, the "low-molecular liquid crystal compound" refers to a liquid crystal compound having no repeating unit in the chemical structure.
[0175] Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymer described in JP-A-2011-237513 and the polymer liquid crystal compound described in paragraphs
[0012] to
[0042] of WO-2018 / 199096.
[0176] Examples of the low-molecular liquid crystal compound include the liquid crystal compounds described in paragraphs
[0072] to
[0088] of JP-A-2013-228706, and among these, liquid crystal compounds showing smecticity are preferred.
[0177] Examples of such liquid crystal compounds include those described in paragraphs
[0019] to
[0140] of International Publication No. 2022 / 014340, and these descriptions are incorporated into this specification by reference.
[0178] The content of the liquid crystal compound is preferably 50 to 99% by mass, more preferably 75 to 90% by mass, based on the total mass of the light absorption anisotropic layer.
[0179] <Dichroic substances>
[0180] In the present invention, a dichroic substance refers to a pigment whose absorbance differs depending on the direction. A dichroic substance may or may not exhibit liquid crystallinity.
[0181] There is no particular limitation on dichroic substances, and examples thereof include visible light absorbing substances (dichroic pigments), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet absorbing substances, infrared absorbing substances, nonlinear optical substances, carbon nanotubes and inorganic substances (such as quantum rods), etc. Conventionally known dichroic substances (dichroic pigments) can be used.
[0182] Specifically, for example, paragraphs
[0067] to
[0071] of Japanese Patent Application Laid-Open No. 2013-228706, paragraphs
[0008] to
[0026] of Japanese Patent Application Laid-Open No. 2013-227532, paragraphs
[0008] to
[0015] of Japanese Patent Application Laid-Open No. 2013-209367, paragraphs
[0045] to
[0058] of Japanese Patent Application Laid-Open No. 2013-14883, paragraphs
[0012] to
[0029] of Japanese Patent Application Laid-Open No. 2013-109090, paragraphs
[0009] to
[0017] of Japanese Patent Application Laid-Open No. 2013-101328, and paragraphs
[0051] to
[0065] of Japanese Patent Application Laid-Open No. 2013-37353. , paragraphs
[0049] to
[0073] of Japanese Patent Application Laid-Open No. 2012-63387, paragraphs
[0016] to
[0018] of Japanese Patent Application Laid-Open No. 11-305036, paragraphs
[0009] to
[0011] of Japanese Patent Application Laid-Open No. 2001-133630, paragraphs
[0030] to
[0169] of Japanese Patent Application Laid-Open No. 2011-215337, paragraphs
[0021] to
[0075] of Japanese Patent Application Laid-Open No. 2010-106242, paragraphs
[0011] to
[0025] of Japanese Patent Application Laid-Open No. 2010-215846, paragraphs
[0017] to
[0069] of Japanese Patent Application Laid-Open No. 2011-048311, paragraphs
[0018] to
[0069] of Japanese Patent Application Laid-Open No. 2011- 213610, paragraphs
[0013] to
[0133] of Japanese Patent Application Publication No. 2011-237513, paragraphs
[0074] to
[0246] of Japanese Patent Application Publication No. 2016-006502, paragraphs
[0005] to
[0051] of Japanese Patent Application Publication No. 2018-053167, paragraphs
[0014] to
[0032] of Japanese Patent Application Publication No. 2020-11716, paragraphs
[0005] to
[0041] of International Publication No. 2016 / 060173, paragraphs
[0008] to
[0062] of International Publication No. 2016 / 136561, International Publication No. 2017 / 154835 paragraphs
[0014] to
[0033] of International Publication No. 2017 / 154695, paragraphs
[0014] to
[0033] of International Publication No. 2017 / 195833, paragraphs
[0014] to
[0034] of International Publication No. 2018 / 164252, paragraphs
[0021] to
[0030] of International Publication No. 2018 / 186503, paragraphs
[0043] to
[0063] of International Publication No. 2019 / 189345, paragraphs
[0043] to
[0085] of International Publication No. 2019 / 225468, paragraphs
[0050] to
[0074] of International Publication No. 2020 / 004106,The contents described in paragraphs
[0015] to
[0038] of International Publication No. 2021 / 044843.
[0183] In the present invention, from the viewpoint of improving dichroism, it is preferred to use a dichroic azo dye compound as the dichroic substance, and it is more preferred to use a dichroic azo dye compound having a thienothiazole skeleton.
[0184] A dichroic azo dye compound refers to an azo dye compound whose absorbance varies according to the direction. A dichroic azo dye compound may or may not exhibit liquid crystallinity. When a dichroic azo dye compound exhibits liquid crystallinity, it may exhibit either nematicity or smecticity. The temperature range in which the liquid crystal phase is exhibited is preferably room temperature (about 20 to 28° C.) to 300° C., and more preferably 50 to 200° C. from the viewpoint of operability and manufacturing applicability.
[0185] In the present invention, from the viewpoint of color tone adjustment, it is preferred to use at least one pigment compound (first dichroic azo pigment compound) having a maximum absorption wavelength in the wavelength range of 560 to 700 nm and at least one pigment compound (second dichroic azo pigment compound) having a maximum absorption wavelength in the wavelength range of greater than 455 nm and less than 560 nm.
[0186] In the present invention, three or more dichroic azo dye compounds may be used simultaneously. For example, from the viewpoint of making the light absorption anisotropic layer close to black, it is preferred to simultaneously use a first dichroic azo dye compound, a second dichroic azo dye compound, and at least one dye compound (third dichroic azo dye compound) having a maximum absorption wavelength in the range of greater than 380 nm and less than 455 nm.
[0187] In the present invention, the dichroic azo dye compound preferably has a crosslinkable group.
[0188] Examples of the crosslinkable group include a (meth)acryloyl group, an epoxy group, an oxetanyl group, and a styryl group. Among them, a (meth)acryloyl group is preferred.
[0189] The content of the dichroic substance is not particularly limited, but from the reason that the orientation degree of the formed light absorption anisotropic layer becomes high, it is preferably 3 mass% or more, more preferably 8 mass% or more, and further preferably 10 mass% or more relative to the total mass of the light absorption anisotropic layer. The upper limit of the content of the dichroic substance is not particularly limited, but it is preferably 30 mass% or less, more preferably 29 mass% or less, and further preferably 25 mass% or less relative to the total mass of the light absorption anisotropic layer. In addition, when a plurality of dichroic substances are used simultaneously, the total amount of the plurality of dichroic substances is preferably within the above range.
[0190] Furthermore, the content of the dichroic substance is preferably 10 to 400 mg / cm because the degree of orientation of the formed light absorption anisotropic layer becomes high. 3 , more preferably 30 to 300 mg / cm 3 , more preferably 40 to 250 mg / cm 3 In addition, when a plurality of dichroic substances are used simultaneously, the total amount of the plurality of dichroic substances is preferably within the above range.
[0191] Here, the content of dichroic substances (mg / cm 3 ) can be obtained by measuring a solution obtained by dissolving an optical laminate having a light absorbing anisotropic layer or an extract obtained by immersing the optical laminate in a solvent using high-speed liquid chromatography (HPLC), but is not limited to the above method. In addition, quantification can be performed by using a dichroic substance contained in the light absorbing anisotropic layer as a standard sample.
[0192] As an example of a method for calculating the content of a dichroic substance, the following method can be cited: the volume is calculated by multiplying the thickness of the light absorption anisotropic layer obtained from a microscope observation image of a cross-section of the optical laminate and the area of the optical laminate used to measure the pigment amount, and the pigment amount measured by HPLC is divided by the volume to calculate the pigment content.
[0193] The thickness of the light absorption anisotropic layer is not particularly limited, but is preferably 0.1 to 10 μm, more preferably 0.5 to 5 μm.
[0194] <Method for producing light-absorbing anisotropic layer>
[0195] The method for producing a light-absorbing anisotropic layer is not particularly limited, but from the viewpoint of increasing the degree of orientation of the dichroic substance, a method preferably includes the following steps in sequence (hereinafter also referred to as "the present production method"): a step of coating a composition for forming a light-absorbing anisotropic layer containing a liquid crystal compound and a dichroic substance on the above-mentioned orientation film to form a coating film (hereinafter also referred to as "coating film forming step"); and a step of orienting the liquid crystal component contained in the above-mentioned coating film (hereinafter also referred to as "orientation step").
[0196] The liquid crystal component is a component containing not only the above-mentioned liquid crystal compound but also a dichroic substance having liquid crystallinity.
[0197] Hereinafter, each step will be described.
[0198] The coating film forming step is a step of coating the above-mentioned light absorption anisotropic layer-forming composition on the alignment film to form a coating film.
[0199] By using a light-absorbing anisotropic layer-forming composition containing the above-mentioned solvent or a light-absorbing anisotropic layer-forming composition obtained by heating or the like to be melted into a liquid, the light-absorbing anisotropic layer-forming composition can be easily coated on the alignment film.
[0200] Examples of the coating method for the light absorption anisotropic layer-forming composition include known methods such as roll coating, gravure printing, spin coating, wire bar coating, extrusion coating, direct gravure coating, reverse gravure coating, die coating, spray coating, and inkjet.
[0201] The alignment step is a step of aligning the liquid crystal component (particularly, the dichroic substance) contained in the coating film. In the alignment step, it is considered that the dichroic substance is aligned along the liquid crystal compound aligned by the alignment film.
[0202] The orientation process may include a drying process. By drying, components such as solvents can be removed from the coating film. The drying process may be performed by leaving the coating film at room temperature for a predetermined time (e.g., natural drying), or by heating and / or blowing air.
[0203] The orientation step preferably includes a heat treatment. This further orients the dichroic substance contained in the coating film, and the degree of orientation of the dichroic substance further increases.
[0204] From the viewpoint of production suitability, the heat treatment is preferably performed at 10 to 250° C., more preferably 25 to 190° C. The heating time is preferably 1 to 300 seconds, more preferably 1 to 60 seconds.
[0205] The orientation process may include a cooling process performed after the heating process. The cooling process is a process of cooling the heated coating film to about room temperature (20 to 25° C.). As a result, the orientation of the dichroic substance contained in the coating film is further fixed, and the degree of orientation of the dichroic substance is further increased. There is no particular limitation on the cooling method, and it can be performed by a known method.
[0206] Through the above steps, a light absorption anisotropic layer can be obtained.
[0207] The present production method may include a step of curing the light absorption anisotropic layer after the alignment step (hereinafter also referred to as a “curing step”).
[0208] The curing step can be performed, for example, by heating and / or light irradiation (exposure). Among them, the curing step is preferably performed by light irradiation.
[0209] As the light source for curing, various light sources such as infrared, visible light or ultraviolet light can be used, preferably ultraviolet light. In addition, during curing, ultraviolet light may be irradiated while heating, or ultraviolet light may be irradiated through a filter that transmits only a specific wavelength.
[0210] Furthermore, the exposure may be performed in a nitrogen atmosphere. When the light absorption anisotropic layer is cured by radical polymerization, the polymerization hindrance caused by oxygen can be reduced, so the exposure is preferably performed in a nitrogen atmosphere.
[0211] 〔Protective layer〕
[0212] In the laminate of the present invention, it is preferred that the light absorption anisotropic layer has an oxygen permeability of 200 cc / m on the side opposite to the oriented film for the purpose of improving durability. 2 The protective layer with a relative humidity of less than 100 % is preferably provided with an oxygen permeability coefficient of 50 cc / m 2 ·day·atm below the protection layer.
[0213] Furthermore, if there is a layer other than the above-mentioned protective layer having properties equivalent to those of the protective layer, the protective layer may not be provided.
[0214] Here, the oxygen permeability coefficient is an index indicating the amount of oxygen passing through the membrane per unit time and per unit area. In the present invention, the value measured by an oxygen concentration device (e.g., MODEL3600 manufactured by Hach UltraAnalytics, Inc.) under an environment of 25°C and 50% relative humidity (RH) is used.
[0215] Specifically, for example, the protective layer includes films containing organic compounds such as polyvinyl alcohol resins, polyethylene-vinyl alcohol resins, polyvinyl ethers, polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, cellulose ethers, polyamides, polyimides, styrene / maleic acid copolymers, gelatin, vinylidene chloride, and cellulose nanofibers.
[0216] Among these, a polyvinyl alcohol-based resin film or a polyethylene-vinyl alcohol-based resin film is preferred because of its high oxygen barrier capability, and a polyvinyl alcohol-based resin film is more preferred.
[0217] As the organic compound contained in the protective layer, from the reason of high oxygen barrier function, there can be mentioned polymerizable compounds with high hydrogen bonding properties and compounds having a large number of polymerizable groups per unit molecular weight. As the compound having a large number of polymerizable groups per unit molecular weight, for example, there can be mentioned pentaerythritol tetra(meth)acrylate or dipentaerythritol hexa(meth)acrylate.
[0218] Examples of polymerizable compounds having high hydrogen bonding properties include epoxy compounds, and specifically, for example, compounds represented by the following formulas. Among them, 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate represented by the following CEL2021P is preferred.
[0219] [Chemical formula 3]
[0220]
[0221]
[0222] As a protective layer, from the viewpoint of preventing the diffusion of the dichroic dye of the light absorption anisotropic layer during durability, it is also preferred to use a polymer having a hydrophilic group described in paragraph
[0056] of International Publication No. 2019-22121 or a water-soluble polymer described in paragraphs
[0117] to
[0133] of Japanese Patent Application Laid-Open No. 2017-083483.
[0223] [Adhesive layer]
[0224] The laminate of the present invention may or may not have a tacky adhesive layer.
[0225] Examples of the adhesive agent constituting the adhesive layer include adhesives and pressure-sensitive adhesives.
[0226] As the adhesive, for example, rubber adhesives, acrylic adhesives, silicone adhesives, urethane adhesives, vinyl alkyl ether adhesives, polyvinyl alcohol adhesives, polyvinyl pyrrolidone adhesives, polyacrylamide adhesives and cellulose adhesives can be mentioned, and acrylic adhesives (pressure-sensitive adhesives) are preferred.
[0227] As the adhesive, for example, water-based adhesives, solvent-based adhesives, emulsion-based adhesives, solvent-free adhesives, active energy ray-curable adhesives, and thermosetting adhesives can be cited. As the active energy ray-curable adhesive, electron beam-curable adhesives, ultraviolet-curable adhesives, and visible light-curable adhesives can be cited, and ultraviolet-curable adhesives are preferred.
[0228] The thickness of the adhesive layer is not particularly limited, but is preferably 25 μm or less, more preferably 15 μm or less, and further preferably 5 μm or less from the viewpoint of thinning. The lower limit is not particularly limited, but is often 0.1 μm or more.
[0229] From the viewpoint of simplifying and thinning the structure of the laminate, it is also preferred to provide the adhesive layer with a function of improving the durability of the protective layer so that the light absorption anisotropic layer is adjacent to the adhesive layer without providing a protective layer. For example, a structure in which an orientation layer, a light absorption anisotropic layer, an adhesive layer and a phase difference layer are arranged adjacent to each other in this order can be cited.
[0230] Furthermore, as the adhesive layer, the diffusion prevention function of the dichroic dye in the light absorption anisotropic layer can be imparted during durability. In order to exert the above diffusion prevention function, for example, the oxygen permeability coefficient of the adhesive layer is preferably set to 200 cc / m 2 ·day·atm or less, more preferably 50cc / m 2 ·day·atm or less.
[0231] Examples of the adhesive layer having the above diffusion prevention function include an adhesive containing polyvinyl alcohol as a main component, a UV adhesive having a low oxygen permeability, and an adhesive containing a polymer having a hydrophilic group.
[0232] [Method for producing laminated body]
[0233] The method for manufacturing a laminate of the present invention comprises: an alignment film forming step, forming an alignment film on a substrate using an alignment film forming composition; a light absorption anisotropic layer forming step, after the alignment film forming step, forming a light absorption anisotropic layer on the alignment film using a light absorption anisotropic layer forming composition containing a liquid crystal compound and a dichroic substance; and a substrate stripping step, after the light absorption anisotropic layer forming step, stripping the substrate to produce a laminate of the alignment film and the light absorption anisotropic layer.
[0234] Hereinafter, each step included in the method for producing a laminated body of the present invention will be described.
[0235] [Orientation film formation process]
[0236] <Base Material>
[0237] The substrate used in the alignment film forming step is not particularly limited, and a known substrate can be used. In particular, a transparent substrate is preferably used. In addition, a transparent substrate refers to a substrate with a visible light transmittance of 60% or more, preferably 80% or more, and more preferably 90% or more.
[0238] Examples of the substrate include a glass substrate and a polymer film.
[0239] As materials for the polymer film, for example, cellulose polymers can be cited; acrylic polymers having acrylate polymers such as polymethyl methacrylate and polymers containing lactone rings; thermoplastic norbornene polymers; polycarbonate polymers; polyester polymers such as polyethylene terephthalate and polyethylene naphthalate; styrene polymers such as polystyrene and acrylonitrile-styrene copolymers; polyolefin polymers such as polyethylene, polypropylene and ethylene-propylene copolymers; vinyl chloride polymers; amide polymers such as nylon and aromatic polyamide; imide polymers; sulfone polymers; polyethersulfone polymers; polyetheretherketone polymers; polyphenylene sulfide polymers; vinylidene chloride polymers; vinyl alcohol polymers; vinyl butyral polymers; arylate polymers; polyoxymethylene polymers; epoxy polymers; or polymers obtained by mixing these polymers, etc.
[0240] Furthermore, the substrate may be a releasable substrate (pseudo support).
[0241] Among these, cellulose-based polymers are preferred, and polymer films using cellulose acylate-based polymers (cellulose acylate-based films) are particularly preferred.
[0242] The thickness of the substrate is not particularly limited, but is preferably 10 to 100 μm, more preferably 30 to 80 μm.
[0243] <Orientation Film Forming Composition>
[0244] The composition for forming an alignment film is not particularly limited. For example, in the case of forming a photoalignment film which is a preferred form of the alignment film, as described above, examples include a composition containing a photoalignment compound (especially a photosensitive compound having a photoalignment group), a polymerization initiator and a solvent.
[0245] In the present invention, it is preferred that the composition for forming an alignment film contains the above-mentioned polymer compound, and the absolute value of the difference between the SP value of the above-mentioned polymer compound and the SP value of the above-mentioned substrate is 1.7 MPa, because the substrate can be easily peeled off in the substrate peeling step described later. 1 / 2 The lower limit is not particularly limited, but 0 is an example.
[0246] Here, the SP value refers to the non-dispersion force component δa of the SP value calculated by the method of Hoy et al. (see Van Krevelen, DW., “Properties of Polymers (ED. 3)”, published by Elseville (1990)).
[0247] That is, the δa value can be calculated by the following formula (X) using the three-dimensional SP values (δd, δp, δh) calculated by the method of Hoy et al.
[0248] δa=(δp 2 +δh 2 ) 0.5 Formula (X)
[0249] According to the method of Hoy et al., the values of δd, δp, and δh can be calculated from the chemical structural formula of the compound to be determined.
[0250] In the case of a copolymer composed of a plurality of repeating units, the square value of the three-dimensional SP value (δd 2 ,δp 2 ,δh 2 ) multiplied by the volume fraction of each repeating unit and summed to calculate the square value of the three-dimensional SP value of the copolymer (δd 2 ,δp 2 ,δh 2 ), and by substituting the square value into the above formula (X), the δa value of the copolymer can be calculated.
[0251] Furthermore, in the present invention, the viscosity of the composition for forming an alignment film at 25° C. is preferably greater than 2 mPa·s and less than 10 mPa·s, and more preferably greater than 2 mPa·s and less than 5 mPa·s, because it is easy to adjust the thickness variation of the formed alignment film to less than 10%.
[0252] Here, the viscosity of the alignment film-forming composition at 25° C. can be measured using a cone-plate type rotational viscometer in accordance with JIS Z 8803 (2011).
[0253] Furthermore, in the present invention, because it is easier to adjust the thickness variation of the formed oriented film to less than 10%, the oriented film forming process preferably includes a drying treatment of drying the coating film having a solid content concentration of less than 60% using wind at a wind speed of less than 2 m after applying the oriented film forming composition on the substrate.
[0254] Here, the wind speed in the drying process is preferably 2.0 m or less, and more preferably 1.0 m or less.
[0255] The drying treatment can be performed not only on a coating film having a solid content of 60% by mass or less but also on a coating film having a solid content of more than 60% by mass, that is, on a coating film immediately after coating the alignment film forming composition on a substrate.
[0256] In the present invention, the method for forming an alignment film using the alignment film-forming composition is not particularly limited to conditions other than the viscosity of the alignment film-forming composition and the drying process, and a conventionally known method can be employed.
[0257] Specifically, when forming a photo-alignment film which is a preferred embodiment of the alignment film, it can be produced by, for example, the following steps:
[0258] A coating step of coating the alignment film-forming composition on the substrate to form a first coating film;
[0259] a drying step of drying and removing the organic solvent by heating the first coating film to form a first dried film on the substrate; and
[0260] In the light irradiation step, the first dried film is irradiated with polarized ultraviolet light (UV) or non-polarized UV light from an oblique direction with respect to the coating film surface, thereby forming a photo-alignment film from the first dried film.
[0261] <Coating process>
[0262] The coating method in the coating step is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include spin coating, die coating, gravure coating, flexographic printing, and inkjet printing.
[0263] <Drying process>
[0264] The temperature of the drying step is not particularly limited as long as it is a temperature that can dry and remove the organic solvent contained in the first coating film, but when the alignment film forming composition contains a polymerization initiator, it is preferably 120 to 160° C., and more preferably 130 to 150° C. from the viewpoint of inducing a polymerization reaction.
[0265] Furthermore, the time of the drying process is not particularly limited as long as it is a temperature that can dry and remove the organic solvent contained in the first coating film. However, when the composition for forming an oriented film contains a polymerization initiator, from the perspective of allowing the polymerization reaction to proceed sufficiently, it is preferably 30 seconds to 5 minutes, and more preferably 1 minute to 3 minutes.
[0266] <Light irradiation step>
[0267] In the light irradiation step, the polarized light irradiated to the first dried film is not particularly limited, and examples thereof include linearly polarized light, circularly polarized light, and elliptically polarized light. Among them, linearly polarized light is preferred.
[0268] The "oblique direction" of irradiating non-polarized light is not particularly limited as long as it is a direction inclined at a polar angle θ (0<θ<90°) relative to the normal direction of the coating surface, and can be appropriately selected depending on the purpose, but θ is preferably 20 to 80°.
[0269] The wavelength of the polarized light or the non-polarized light is not particularly limited as long as it can impart alignment control capability to the first dried film on the liquid crystal molecules, and examples thereof include ultraviolet light, near ultraviolet light, and visible light, among which near ultraviolet light of 250 nm to 450 nm is particularly preferred.
[0270] Furthermore, as a light source for irradiating polarized light or non-polarized light, for example, a xenon lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, etc. can be cited. By using an interference filter or a color filter, etc. on ultraviolet light or visible light obtained from such a light source, the wavelength range of irradiation can be limited. Furthermore, by using a polarizing film or a polarizing prism on the light from these light sources, linear polarized light can be obtained.
[0271] The accumulated light intensity of polarized light or non-polarized light is not particularly limited as long as it can impart alignment control capability to the first dried film on liquid crystal molecules, but is preferably 1 to 300 mJ / cm 2 , more preferably 5 to 100 mJ / cm 2 .
[0272] The illuminance of polarized light or non-polarized light is not particularly limited as long as it can impart alignment control capability to the first dried film for liquid crystal molecules, but is preferably 0.1 to 300 mW / cm 2 , more preferably 1 to 100 mW / cm 2 .
[0273] [Virtual reality display device]
[0274] As an example of the virtual reality display device of the present invention (first mode), there can be cited a virtual reality display device which sequentially comprises an image display panel, a first absorption-type linear polarizer, a first phase difference layer, a reflection-type circular polarizer, a half mirror, a second phase difference layer and a second absorption-type linear polarizer.
[0275] Furthermore, as another example (second mode), there can be cited a virtual reality display device which sequentially comprises an image display panel, a first absorption type linear polarizer, a first phase difference layer, a second phase difference layer, a reflection type linear polarizer, a third phase difference, a half mirror and a second absorption type linear polarizer.
[0276] Furthermore, as another example (third mode), there can be cited a virtual reality display device which sequentially comprises an image display panel, a first absorbing linear polarizer, a first phase difference layer, a half mirror, a reflective circular polarizer, a second phase difference layer and a second absorbing linear polarizer.
[0277] Furthermore, as another example (the fourth mode), there can be cited a virtual reality display device which sequentially comprises an image display panel, a first absorbing linear polarizer, a first phase difference layer, a half mirror, a second phase difference layer, a reflecting linear polarizer and a second absorbing linear polarizer.
[0278] Furthermore, in the virtual reality display device of the present invention, the second absorbing linear polarizer is the above-mentioned laminate of the present invention.
[0279] Furthermore, the virtual reality display device of the present invention preferably includes a third phase difference layer between the image display panel and the first absorbing linear polarizer.
[0280] Furthermore, the virtual reality display device of the present invention also preferably has a fourth phase difference layer on the visual recognition side of the second absorbing linear polarizer.
[0281] Figure 2 A schematic cross-sectional view showing an example of a virtual reality display device of the present invention is shown in FIG.
[0282] Figure 2 The virtual reality display device 100 shown is a virtual reality display device which sequentially comprises an image display panel 70, a first absorption type linear polarizer 21, a first phase difference layer 11, a reflection type circular polarizer 30, a half mirror 40, a second phase difference layer 12 and a second absorption type linear polarizer 22.
[0283] and, Figure 2 The virtual reality display device 100 shown includes a third phase difference layer 13 between the image display panel 70 and the first absorbing linear polarizer 21 .
[0284] and, Figure 2 The virtual reality display device 100 shown includes an anti-reflection layer 50 and a positive C-plate 60 .
[0285] 〔Image display panel〕
[0286] As the image display panel, a known image display panel can be used, for example, an organic electroluminescent display panel, an LED (Light Emitting Diode) display panel, a micro-LED display panel, or a display panel in which self-luminous micro-light emitters are arranged on a transparent substrate; a liquid crystal display panel; etc.
[0287] In the following description, the organic electroluminescent display device is also referred to as OLED. OLED is the abbreviation of "Organic Light Emitting Diode".
[0288] [1st to 3rd phase difference layers]
[0289] The phase difference layer has the function of converting the outgoing light into approximately linear polarized light when circularly polarized light is incident. For example, a λ / 4 phase difference layer in which Re becomes approximately 1 / 4 wavelength at any wavelength in the visible region can be used, and in this case, the in-plane retardation Re(550) at a wavelength of 550 nm is preferably 120 nm to 150 nm, more preferably 125 nm to 145 nm, and further preferably 135 nm to 140 nm.
[0290] Furthermore, a retardation layer having Re of approximately 3 / 4 wavelength or approximately 5 / 4 wavelength is also preferred because it can convert linearly polarized light into circularly polarized light.
[0291] Furthermore, the phase difference layer preferably has inverse wavelength dispersion with respect to wavelength. If it has inverse wavelength dispersion, it is possible to convert circularly polarized light into linearly polarized light in a wide wavelength range in the visible region, so it is preferred. Here, having inverse wavelength dispersion with respect to wavelength means that as the wavelength becomes larger, the phase difference value at the wavelength also becomes larger.
[0292] The phase difference layer having an inverse wavelength dispersion property can be produced by uniaxially stretching a polymer film such as a modified polycarbonate resin film having an inverse wavelength dispersion property, for example, with reference to Japanese Patent Application Laid-Open No. 2017-049574.
[0293] Furthermore, as long as the phase difference layer having inverse wavelength dispersion is substantially inverse wavelength dispersion, for example, as disclosed in Japanese Patent No. 6259925, it can also be produced by stacking a phase difference layer having Re of approximately 1 / 4 wavelength and a phase difference layer having Re of approximately 1 / 2 wavelength so that their slow axes form an angle of approximately 60° with each other. It is known that at this time, even if the 1 / 4 wavelength phase difference layer and the 1 / 2 wavelength phase difference layer are respectively of a straight dispersion (as the wavelength increases, the phase difference value at the wavelength decreases), circularly polarized light can be converted into linearly polarized light within a wide wavelength range in the visible region, and can be regarded as substantially having inverse wavelength dispersion.
[0294] Furthermore, the phase difference layer also preferably has a layer formed by fixing a uniformly oriented liquid crystal compound. For example, a layer obtained by uniformly aligning a rod-shaped liquid crystal compound horizontally to the in-plane direction, and a layer obtained by uniformly aligning a disc-shaped liquid crystal compound vertically to the in-plane direction can be used. In addition, for example, it is also possible to make a phase difference layer with anti-wavelength dispersion by uniformly aligning and fixing a rod-shaped liquid crystal compound with anti-wavelength dispersion with reference to Japanese Patent Publication No. 2020-084070.
[0295] Furthermore, the phase difference layer also preferably has a layer formed by fixing a liquid crystal compound twisted and oriented with the thickness direction as the helical axis. For example, as disclosed in Japanese Patent No. 5753922, Japanese Patent No. 5960743, etc., a phase difference layer having a layer formed by fixing a rod-shaped liquid crystal compound or a disc-shaped liquid crystal compound twisted and oriented with the thickness direction as the helical axis can be used. In this case, the phase difference layer can be regarded as having substantially anti-wavelength dispersion, and therefore is preferred.
[0296] The thickness of the retardation layer is not particularly limited, but is preferably 0.1 to 8 μm, more preferably 0.3 to 5 μm, from the viewpoint of thinning.
[0297] 〔Positive C layer〕
[0298] The positive C plate preferably has a thickness direction retardation (Rth(550)) of -150 to -50 nm at a wavelength of 550 nm. By including such a positive C plate, light leakage and color shift in an oblique viewing direction of the display device can be further suppressed.
[0299] The retardation in the thickness direction of the positive C plate at a wavelength of 550 nm (Rth(550)) is -150 to -50 nm, preferably -130 to -60 nm, and more preferably -120 to -70 nm.
[0300] The thickness of the positive C plate is not particularly limited, but from the viewpoint of thinning, it is preferably 0.5 to 10 μm, and more preferably 0.5 to 5 μm. In addition, when the positive C plate is provided, the positive C plate may be provided alone by transfer or coating, but other functional layers may be provided together with the positive C plate as required. The functional layer may be a protective film, a hard coating layer, or a buffer layer. As the protective film, each of the films cited as the protective film of the polarizer described above can be used.
[0301] The material constituting the positive C plate is not particularly limited, but is preferably formed from a composition containing a liquid crystal compound. From the viewpoint of increasing durability over time and orientation order, it is preferably formed from a polymerizable liquid crystal composition containing a polymerizable liquid crystal compound. Such a positive C plate can typically be obtained by vertically aligning the rod-shaped polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition and fixing the orientation state by polymerization. Furthermore, it can also be formed from a composition containing a side chain polymer liquid crystal compound as a liquid crystal compound.
[0302] 〔Absorption type linear polarizer〕
[0303] The absorption type linear polarizer is an absorption type polarizer, which absorbs linear polarized light in the absorption axis direction of the incident light and transmits linear polarized light in the transmission axis direction. As the absorption type linear polarizer, a common polarizer can be used, for example, a polarizer in which a dichroic substance is dyed with polyvinyl alcohol or other polymer resins and oriented by stretching, or a polarizer in which a dichroic substance is oriented by the orientation of a liquid crystal compound. From the viewpoint of availability and the viewpoint of improving the polarization degree, a polarizer in which polyvinyl alcohol is dyed with iodine and stretched is preferred.
[0304] Furthermore, in the present invention, the above-mentioned laminate of the present invention is used as the second absorbing linear polarizer.
[0305] The thickness of the absorbing linear polarizer is preferably 10 μm or less, more preferably 7 μm or less, and further preferably 5 μm or less. If the absorbing linear polarizer is thin, cracks or breaks in the film can be prevented when the laminated optical film is stretched or molded.
[0306] Furthermore, the single plate transmittance of the absorption type linear polarizer is preferably 40% or more, more preferably 42% or more. Furthermore, the polarization degree is preferably 90% or more, more preferably 95% or more, and further preferably 99% or more. In addition, in this specification, the single plate transmittance and polarization degree of the absorption type linear polarizer are measured using an automatic polarization film measuring device: VAP-7070 (manufactured by JASCO Corporation).
[0307] Furthermore, the direction of the transmission axis of the absorption type linear polarizer is preferably consistent with the direction of the polarization axis of the light converted into linear polarized light by the phase difference layer. For example, when the absorption type phase difference layer has a phase difference of λ / 4, the angle between the transmission axis of the absorption type linear polarizer and the slow axis of the λ / 4 phase difference layer is preferably approximately 45°.
[0308] 〔Half mirror〕
[0309] The half mirror is a conventionally known half mirror that transmits approximately half of the incident light and reflects approximately the remaining half. The transmittance of the half mirror is preferably 50±30%, more preferably 50±10%, and most preferably 50%.
[0310] As a half mirror, for example, a structure in which a reflective layer composed of metals such as silver and aluminum is provided on a substrate composed of a transparent resin such as polyethylene terephthalate (PET), cycloolefin polymer (COP), polymethyl methacrylate (PMMA), or glass can be cited. The reflective layer composed of metals such as silver and aluminum can be formed on the surface of the substrate by vapor deposition or the like.
[0311] The thickness of the reflective layer is preferably 1 to 20 nm, more preferably 2 to 10 nm, and further preferably 3 to 6 nm.
[0312] Furthermore, the substrate preferably has no phase difference. From this viewpoint, the substrate of the half mirror is preferably cycloolefin polymer (COP), polymethyl methacrylate (PMMA) or glass.
[0313] 〔Reflective circular polarizer〕
[0314] The reflective circular polarizer is a polarizer that transmits right-handed circularly polarized light or left-handed circularly polarized light and reflects circularly polarized light having a rotation direction opposite to that of the transmitted circularly polarized light.
[0315] As a reflective circular polarizer, a reflective circular polarizer having a cholesteric liquid crystal layer is exemplified as an example. The cholesteric liquid crystal layer is a liquid crystal phase in which a cholesterically aligned liquid crystal phase (cholesteric liquid crystal phase) is fixed.
[0316] As is known to all, the cholesteric liquid crystal layer has a spiral structure in which liquid crystal compounds are stacked in a spiral rotation, and the structure in which the liquid crystal compounds are stacked in a spiral rotation of one circle (360° rotation) is regarded as one spiral period (spiral period), and the liquid crystal compounds rotating in a spiral rotation have a structure in which multiple periods are stacked.
[0317] The cholesteric liquid crystal layer reflects right-handed circularly polarized light or left-handed circularly polarized light in a specific wavelength range, depending on the length of the helical period and the handedness (sense) of the helix of the liquid crystal compound, and transmits the rest of the light.
[0318] Therefore, when the virtual reality display device displays a color image, the reflective circular polarizer can, for example, have a multi-layer cholesteric liquid crystal layer having a central wavelength that selectively reflects red light, a cholesteric liquid crystal layer having a central wavelength that selectively reflects green light, and a cholesteric liquid crystal layer having a central wavelength that selectively reflects blue light.
[0319] Furthermore, when the reflective circular polarizer has a cholesteric liquid crystal layer, it may have a support and an alignment film for aligning the liquid crystal compound in the cholesteric liquid crystal layer.
[0320] The thickness of the reflective circular polarizer may be appropriately adjusted to a thickness that can sufficiently reflect polarized light to be reflected and sufficiently transmit polarized light to be transmitted, depending on the type of the reflective circular polarizer and the like.
[0321] 〔Reflective linear polarizer〕
[0322] The virtual reality display device of the present invention can include a reflective linear polarizer. In a part of the optical system, the reflective linear polarizer can play the following function: reflect a part of the light emitted from the image display panel, so that it travels back and forth inside the optical system, thereby lengthening the optical path length. From the viewpoint of suppressing stray light and ghosting, the reflective linear polarizer is preferably a polarizer with a high degree of polarization.
[0323] As the reflective linear polarizer, a film obtained by stretching a dielectric multilayer film as described in Japanese Patent Application Laid-Open No. 2011-053705 and a wire grid polarizer etc. can be used. As commercially available products, a reflective polarizer (trade name APF, IQPE) manufactured by 3M Company, a wire grid polarizer (trade name WGF) manufactured by Asahi Kasei Corporation etc. can be appropriately used.
[0324] The virtual reality display device of the present invention can use a curved substrate as a base material (for example, Figure 2 The component between the second phase difference layer 12 and the half mirror 40).
[0325] Here, the curved surface shape refers to a shape with a curvature exceeding 0, including a curved surface shape as an expandable curved surface and a three-dimensional curved surface shape. An expandable curved surface refers to a surface that can be expanded into a plane without stretching the parts of the surface. As a curved surface shape, for example, a part or all of the surfaces corresponding to the circumference of a cylinder, the circumference of an elliptical cylinder, the circumference of a cone, and the circumference of an elliptical cone can be cited. It can be a convex curved surface or a concave curved surface. A three-dimensional curved surface refers to a curved surface that cannot be obtained by plane deformation, that is, a curved surface that is not an expandable curved surface. As a three-dimensional curved surface shape, a part or all of the surfaces corresponding to the sphere and the ellipsoid, a part or all of the surfaces corresponding to the curved surface with a parabola or hyperbola in cross section can be cited. It can be a convex curved surface or a concave curved surface. In addition, as long as the curved substrate has a curved surface shape in at least a part thereof, it can be a shape formed by combining a plane shape and a curved surface shape, or it can be a curved surface shape as a whole. Furthermore, the curved surface shape included in the curved substrate may be composed only of any one of a curved surface shape as a developable curved surface or a three-dimensional curved surface shape, or may be composed of a combination of a curved surface as a developable curved surface and a three-dimensional curved surface, or a combination of a curved surface as a developable curved surface and / or a three-dimensional curved surface and a plane.
[0326] In one embodiment of the present invention, the curved surface shape of the curved substrate is preferably a lens shape. The lens-shaped curved surface shape refers to a curved surface shape with a constant curvature in all directions on the curved surface. As the lens-shaped curved surface shape, for example, a spherical surface, an ellipsoidal surface, a hemispherical surface, a semi-ellipsoidal surface, etc. can be cited, and it can be a convex lens shape or a concave lens shape.
[0327] In one embodiment of the present invention, the curved substrate preferably satisfies the formula (1).
[0328] 20mm≤R≤300mm (1)
[0329] [In formula (1), R represents the radius of curvature of the portion with the smallest curvature in the curved substrate.]
[0330] Formula (1) means that the radius of curvature of the most gentle curved surface possessed by the curved substrate is more than 20 mm and less than 300 mm. The radius of curvature R (hereinafter, also referred to as "radius of curvature R") of the part with the smallest curvature in the curved substrate can be, for example, less than 250 mm, or less than 200 mm. In addition, the radius of curvature R is more preferably more than 25 mm, and more preferably more than 30 mm. If the radius of curvature R is more than the above lower limit, it is easier to improve stackability.
[0331] In the curved substrate, the radius of curvature R' of the portion with the largest curvature (hereinafter, also referred to as "radius of curvature R'") is preferably 10 mm or more, more preferably 15 mm or more, further preferably 20 mm or more, particularly preferably 25 mm or more, and particularly preferably 30 mm or more. The radius of curvature R' may be, for example, 250 mm or less, 200 mm or less, or 150 mm or less.
[0332] In addition, when the curved surface shape included in the curved substrate is a shape having the same curvature in all directions of the curved surface, such as a lens-shaped curved surface shape, its curvature radius R" is usually greater than the lower limit value of the above-mentioned curvature radius R' and less than the upper limit value of the above-mentioned curvature radius R.
[0333] As long as the curved substrate is made of the material that can form the desired curved surface shape, it is not particularly limited, and according to the purposes of the desired curved surface shape, polaroid, etc., it can be suitably selected from known materials. For example, glass substrate, film substrate, metal substrate, etc. can be enumerated. From the viewpoint of easily forming various curved surface shapes, the curved substrate is preferably made of glass substrate or film substrate, more preferably made of glass substrate or resin film substrate.
[0334] Examples of the light-transmitting substrate include a glass substrate and a transparent resin film substrate.
[0335] As the resin constituting the resin film substrate, for example, polyolefins such as polyethylene, polypropylene, and norbornene polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylate; polyacrylate; cellulose ester; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene oxide, etc. From the viewpoint of forming a polarizer, a glass substrate or a material having a hardness similar to that thereof is more suitable as the substrate.
[0336] The surface of the surface substrate may be subjected to surface treatment such as corona treatment, plasma treatment, mold release treatment such as silicone treatment, etc. Furthermore, the substrate surface on the side where the polarizer is not laminated may be subjected to hard coating treatment, antireflection treatment, antistatic treatment, etc.
[0337] The thickness of the curved substrate can be appropriately determined according to the curved shape, the material constituting the curved substrate, the purpose of the virtual reality display device, etc. The curved substrate can have the same thickness as a whole, or it can have different thicknesses. The thickness of the curved substrate is, for example, 30 μm to 5 cm, preferably 100 μm to 3.5 cm, and more preferably 500 μm to 3 cm.
[0338] Example
[0339] Below, the present invention is further described in detail based on embodiment.As long as the material, usage amount, ratio, processing content, processing step etc. shown in the following embodiment do not depart from the gist of the present invention, then can be appropriately changed.Therefore, the scope of the present invention should not be interpreted restrictively by the embodiment shown below.
[0340] (First Embodiment of Virtual Reality Display Device)
[0341] [Example 1]
[0342] [Preparation of substrate 1]
[0343] The following composition was placed in a mixing tank and stirred, and then heated at 90°C for 10 minutes. Then, the obtained composition was filtered through a filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm to prepare a doping liquid. The solid content concentration of the doping liquid was 23.5% by mass, the amount of the plasticizer added was the ratio to the cellulose acylate, and the solvent of the doping liquid was dichloromethane / methanol / butanol = 81 / 18 / 1 (mass ratio).
[0344]
[0345] [Chemical formula 4]
[0346]
[0347] [Chemical formula 5]
[0348]
[0349] The dope solution prepared as described above was cast using a roll film machine. The dope solution was cast from the mold so as to contact a metal support cooled to 0° C., and then the obtained coil (film) was peeled from the roll. The roll was made of SUS (stainless steel).
[0350] After the roll (film) obtained by casting was peeled off from the drum and transported, it was dried for 20 minutes in a tenter device at 30 to 40° C. using a clamp holding both ends of the roll and transporting it. Subsequently, the roll was post-dried by zone heating while being transported by rollers. The obtained roll was knurled and then wound up to serve as a substrate 1.
[0351] The obtained substrate 1 had a film thickness of 60 μm, an in-plane retardation Re(550) of 1 nm at a wavelength of 550 nm, and a thickness-direction retardation Rth(550) of 35 nm at a wavelength of 550 nm.
[0352] [Preparation of photo-alignment film B1]
[0353] The photo-alignment film-forming composition B1 described later was continuously applied to the substrate 1 using a wire bar. The support with the coating film was dried for 120 seconds at 140° C. and a wind speed of 1 m / s, and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 , using an ultra-high pressure mercury lamp), thereby producing a photo-alignment film B1, and obtaining a substrate 1 with a photo-alignment film. The thickness of the photo-alignment film B1 was 1.5 μm.
[0354] As shown in Table 3 below, the photo-alignment film-forming composition B1 had a solid content concentration of 20% and a viscosity of 3.5 mPa·s.
[0355] In addition, the secondary ion intensity derived from polymer compound PB-1 was measured by the above method using TOF-SIMS for the produced photo-alignment film, and it was confirmed that polymer compound PB-1 was concentrated on the side opposite to the light absorption anisotropic layer (substrate 1 side).
[0356] The absolute value of the difference between the SP value of the polymer compound PB-1 in the photo-alignment film-forming composition B1 and the SP value of the substrate 1 was 1.5 MPa. 1 / 2 .
[0357] Composition of Photo-Alignment Film-Forming Composition B1
[0358]
[0359] Polymer PA-1 (photo-aligned compound) (weight average molecular weight: 32000)
[0360] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0361] [Chemical formula 6]
[0362]
[0363] Thermal cationic polymerization initiator PAG-1
[0364] [Chemical formula 7]
[0365]
[0366] Stabilizer DIPEA
[0367] [Chemical formula 8]
[0368]
[0369] Polymer compound PB-1 (weight average molecular weight: 18000)
[0370] [Chemical formula 9]
[0371]
[0372] Acid-cleavable surfactant SA-1 (The numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units. The weight average molecular weight is 78,000.)
[0373] [Chemical formula 10]
[0374]
[0375] [Formation of light absorption anisotropic layer C1]
[0376] A light absorption anisotropic layer-forming composition C1 having the following composition was continuously applied on the obtained photo-alignment film B1 using a wire bar to form a coating film.
[0377] Next, the coating film was heated at 140° C. for 15 seconds, then at 80° C. for 5 seconds, and then cooled to room temperature (23° C.) Then, the coating film was heated at 75° C. for 60 seconds, and then cooled to room temperature again.
[0378] Then, an LED (light emitting diode) lamp (central wavelength 365nm) was used to irradiate at 300mJ, thereby forming a light absorption anisotropic layer C1 (polarizer) (thickness: 1.8μm) on the photo-alignment film B1. In addition, the total content of the first dichroic material Dye-C1, the second dichroic material Dye-M1 and the third dichroic material Dye-Y1 contained in the light absorption anisotropic layer C1 was 220mg / cm 3 .
[0379] The transmittance of the light absorption anisotropic layer C1 in the wavelength region of 280 to 780 nm was measured using a spectrophotometer. As a result, the average visible light transmittance was 42%.
[0380] The absorption axis of the light absorption anisotropic layer C1 is located in the plane of the light absorption anisotropic layer C1 and is orthogonal to the width direction of the cellulose acylate film A1.
[0381]
[0382]
[0383] Dichroic Material Dye-C1
[0384] [Chemical formula 11]
[0385]
[0386] Dichroic Material Dye-M1
[0387] [Chemical formula 12]
[0388]
[0389] Dichroic Material Dye-Y1
[0390] [Chemical formula 13]
[0391]
[0392] Liquid crystal compound L-1 (weight average molecular weight: 18000)
[0393] (In the following formula, the numerical values ("59", "15", "26") described in each repeating unit represent the content (mass %) of each repeating unit relative to all repeating units.)
[0394] [Chemical formula 14]
[0395]
[0396] Liquid crystal compound L-2 (a mixture of the following liquid crystal compounds (RA) (RB) (RC) in a ratio of 84:14:2 (mass ratio))
[0397] [Chemical formula 15]
[0398]
[0399] Adhesion Improver A-1
[0400] [Chemical formula 16]
[0401]
[0402] Surfactant F-1 (weight average molecular weight: 15000)
[0403] (In the formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units. Also, Ac means -C(O)CH3.)
[0404] [Chemical formula 17]
[0405]
[0406] [Formation of protective layer D1]
[0407] A coating liquid D2 having the following composition was continuously applied onto the light absorption anisotropic layer C1 using a wire bar.
[0408] Then, by drying with hot air at 80°C for 5 minutes, a laminated body having a protective layer D1 composed of polyvinyl alcohol (PVA) with a thickness of 0.6 μm was obtained, that is, a laminated body 1 having a substrate 1 (substrate), a photo-alignment film B1, a light absorption anisotropic layer C1 and a protective layer D1 adjacent to each other in sequence.
[0409] In addition, the oxygen permeability coefficient of the protective layer D1 is 6cc / m 2 ·day·atm.
[0410]
[0411] Modified polyvinyl alcohol (weight average molecular weight: 28000)
[0412] (In the following formula, the numerical value described in each repeating unit represents the content (mass %) of each repeating unit relative to all repeating units.)
[0413] [Chemical formula 18]
[0414]
[0415] Surfactant F-9
[0416] [Chemical formula 19]
[0417]
[0418] [Example 2]
[0419] A laminate 2 was prepared in the same manner as in Example 1 except that the following surfactant F-1 (weight average molecular weight: 15,000) was used instead of the acid-cleavable surfactant SA-1 blended in the photo-alignment film-forming composition.
[0420] <Surfactant F-1>
[0421] [Chemical formula 20]
[0422]
[0423] [Example 3]
[0424] A laminate 3 was produced in the same manner as in Example 1 except that the protective layer D1 was not formed.
[0425] [Example 4]
[0426] A laminate 4 was prepared in the same manner as in Example 1 except that the acid-cleavable surfactant SA-1 was not blended in the photo-alignment film-forming composition.
[0427] [Example 5]
[0428] A laminate 5 was prepared in the same manner as in Example 1 except that the acid-cleavable surfactant SA-1 was not blended into the photo-alignment film-forming composition, the blending amount of butyl acetate was adjusted to a solid content concentration of 10%, and the viscosity was adjusted to 1.1 mPa·s.
[0429] [Comparative Example 1]
[0430] A laminate H1 was produced in the same manner as in Example 5 except that the wind speed during drying after applying the photo-alignment film-forming composition was changed from 1 m / s to 6 m / s.
[0431] [Example 6]
[0432] [Formation of light absorption anisotropic layer C2]
[0433] The following components were mixed and stirred at 80° C. for 1 hour to obtain a composition C2 for forming a light absorption anisotropic layer.
[0434]
[0435]
[0436] Among these dichroic substances, the dichroic substance A3 and the dichroic substance A4 are dichroic substances having maximum absorption wavelengths in the wavelength range of 550 to 700 nm.
[0437] Polymerizable liquid crystal compound (1-6)
[0438] [Chemical formula 21]
[0439]
[0440] Polymerizable liquid crystal compound (1-7)
[0441] [Chemical formula 22]
[0442]
[0443] Dichroic substance A1
[0444] [Chemical formula 23]
[0445]
[0446] Dichroic substance A2
[0447] [Chemical formula 24]
[0448]
[0449] Dichroic substance A3
[0450] [Chemical formula 25]
[0451]
[0452] Dichroic substance A4
[0453] [Chemical formula 26]
[0454]
[0455] Next, a slit coater was used to apply the light absorption anisotropic layer forming composition C1 onto the photo-alignment film B1 of the substrate 1 with a photo-alignment film prepared in the same manner as in Example 1 to form a coating film. Furthermore, the coating film was conveyed in a ventilation drying furnace set at 110° C. for 2 minutes to remove the solvent, and then rapidly cooled to form a dry film.
[0456] Then, a high pressure mercury lamp was used to irradiate the 2 The polymerizable liquid crystal contained in the dried film was cured by irradiating with ultraviolet light (365 nm reference), thereby forming a light absorption anisotropic layer C2. In addition, the total content of the dichroic substances A1 to A4 contained in the light absorption anisotropic layer C2 was 50 mg / cm 3 .
[0457] Next, a protective layer D1 similar to that of Example 1 was formed on the light absorption anisotropic layer C2 to obtain a laminate 6 including the substrate 1 (substrate), the photo-alignment film B1, the light absorption anisotropic layer C2, and the protective layer D1 adjacent to each other in this order.
[0458] [evaluate]
[0459] [Film thickness variation]
[0460] Regarding the produced laminate, the film thickness variation of the alignment film was calculated by the above method. The results are shown in Table 3 below.
[0461] 〔Display performance〕
[0462] <Fabrication of retardation layer 1>
[0463] Referring to the method described in paragraphs
[0151] to
[0163] of Japanese Patent Application Laid-Open No. 2020-084070, a retardation layer 1 having reverse wavelength dispersion characteristics was fabricated. In the retardation layer 1, Re = 146 nm and Rth = 73 nm.
[0464] <Fabrication of virtual reality display device>
[0465] Fabrication Figure 2 A virtual reality device having the structure shown was fabricated and confirmed to operate as a virtual reality device. Then, the above virtual reality device was disassembled, and the second absorption type linear polarizer, the second retardation layer, and the half mirror on the visual recognition side were removed. Figure 2 of the second absorption type linear polarizer, the second retardation layer, and the half mirror on the visual recognition side.
[0466] Next, a commercially available laminated film (PAC-3J-30H, thickness 30 μm, manufactured by Sun-A Kaken Co., Ltd.) was adhered to the protective layer side (the photoabsorptive anisotropic layer for the laminate fabricated in Example 3) of each fabricated laminate, and the substrate 1 was peeled off.
[0467] Next, using an adhesive sheet "NCF-D692(5)" manufactured by LINTEC Corporation, the retardation layer 1 was adhered to the exposed photoalignment film side of the laminate.
[0468] Next, a PMMA half mirror was prepared, and using an adhesive sheet "NCF-D692(5)" manufactured by LINTEC Corporation, the laminate was adhered to the side opposite to the reflective surface of the half mirror. After peeling off the laminated film, the fabricated half mirror was assembled into the virtual reality display device.
[0469] <Evaluation of VR image distortion>
[0470] In the fabricated virtual reality display device, a black and white checkerboard pattern was displayed on the image display panel, and the distortion degree of the VR image was visually evaluated according to the following three grades. The results are shown in Table 3 below.
[0471] A: No distortion of the VR image is visible at all
[0472] B: Slight distortion of the VR image is visible, but it does not matter
[0473] C: VR image distortion is visible, but it is not a problem in practical use
[0474] D: The distortion of the VR image is clearly visible
[0475] Durability
[0476] A pressure-sensitive adhesive sheet "NCF-D692(5)" manufactured by LINTEC Corporation was adhered to the protective layer D side (the light absorption anisotropic layer for the laminate produced in Example 3) of each laminate produced, and a commercially available cellulose acylate film (trade name "FUJITAC TG40UL" (produced by FUJIFILM Corporation)) was adhered as a transparent substrate film, and the substrate 1 was peeled off.
[0477] Next, a pressure-sensitive adhesive sheet "NCF-D692(5)" manufactured by LINTEC Corporation was attached to the release surface of the substrate 1 to prepare a sample to be attached to glass. The sample was placed in a constant temperature and humidity chamber and stored at 65°C and 90% RH for 500 hours for a durability test.
[0478] The transmittance change ΔT was calculated from the transmittance values before and after the durability test. It can be said that the closer the ΔT value is to 0, the better the durability. If it is A to C, it is a level with no practical problems. The results are shown in Table 3 below.
[0479] A: Transmittance change is 0.0% or more and less than 1.0%
[0480] B: Transmittance change is 1.0% or more and less than 3.0%
[0481] C: Transmittance change is 3.0% or more and less than 5.0%
[0482] D: Transmittance change is 5.0% or more
[0483] 〔Depression〕
[0484] The obtained laminated film 1m 2 The number of depressions in the was counted. Here, the area on the surface of the photo-alignment film layer where the light absorption anisotropic layer is not formed is set as a depression. Based on the results, the following criteria were used for evaluation. If it is A to B, it is a level without practical problems. The results are shown in Table 3 below.
[0485] A: No more than 3 dents
[0486] B: More than 3 and less than 10 dents
[0487] C: More than 10 depressions
[0488]
[0489] The results shown in Table 3 show that when a laminated body in which the thickness of the alignment film varies by more than 10% is used, a virtual image (VR image) is distorted and display performance is poor (Comparative Example 1).
[0490] On the other hand, it was found that by changing the viscosity and drying conditions of the alignment film-forming composition and using a laminate in which the variation in the thickness of the alignment film was 10% or less, the display performance became good (Examples 1 to 6).
[0491] In particular, from the comparison between Examples 1, 2, and 4, it is found that when an acid-cleavable surfactant is added to the alignment film-forming composition, it is possible to suppress the depression during the formation of the light absorption anisotropic layer.
[0492] Furthermore, from the comparison between Example 1 and Example 3, it can be seen that the durability becomes good when a laminate having a protective layer is used.
[0493] Furthermore, from the comparison between Example 4 and Example 5, it can be seen that if the viscosity of the composition for forming an alignment film is greater than 2 mPa·s and less than 10 mPa·s, it is easy to adjust the thickness variation of the formed alignment film to less than 10%, resulting in better display performance.
[0494] (Third Embodiment of Virtual Reality Display Device)
[0495] [Production of molded body]
[0496] [Production of optically anisotropic films]
[0497] After a commercially available laminating film (PAC-3J-30H, thickness 30 μm, manufactured by Sun-A Kaken Co., Ltd.) was attached to the protective layer side of the laminate 1 , the substrate 1 was peeled off.
[0498] Next, the phase difference layer 1 was laminated using an adhesive sheet "NCF-D692 (5)" manufactured by LINTEC Corporation, and then the support used in the preparation of the phase difference layer 1 was peeled off to prepare an optically anisotropic film with a laminated film 1. At this time, the laminate was laminated so that the absorption axis orientation of the laminate 1 and the slow axis orientation of the phase difference layer 1 were 45°.
[0499] [Production of molded body]
[0500] An adhesive sheet "NCF-D692 (5)" manufactured by LINTEC Corporation was attached to the side of the phase difference layer 1. With the separation film of the adhesive sheet peeled off, the optical anisotropic film 1 with the laminated film was vacuum-formed into a concave surface along a plano-concave lens (made of optical glass) with a diameter of 50 mm and a radius of curvature of 90 mm, with reference to Japanese Patent Publication No. 2012-116094. At this time, the phase difference layer 1 was formed to be in contact with the plano-concave lens. Then, the laminated film was peeled off from the lens to produce a molded body 1 stacked on the plano-concave lens.
[0501] Molded bodies 2 to 5 and molded body H1 were produced by the same method as that for molded body 1 except that laminated body 1 was changed to laminated bodies 2 to 5 and H1.
[0502] [evaluate]
[0503] [Film thickness variation]
[0504] Regarding the produced molded body, the thickness variation of the oriented film formed by the curved surface was calculated while the stage was tilted in the above-mentioned interference film thickness measuring device. At this time, the measurement was performed by measuring 101 points at a distance of 40 mm at any direction passing through the center of the lens at a pitch of 0.4 mm. The results are shown in the following Table 6.
[0505] 〔Fabrication of Reflective Circular Polarizer〕
[0506] <Preparation of Reflective Layer Coating Liquids R-1 to 2 and D-1 to 2>
[0507] The composition shown below was stirred and dissolved in a container maintained at a temperature of 70° C. to prepare a reflective layer coating liquid R-1.
[0508]
[0509] (Reflective layer coating liquid R-2)
[0510] Reflective layer coating liquid R-2 was prepared in the same manner as in the reflective layer coating liquid R-1, except that the addition amount of the chiral agent A was changed as shown in Table 4 below.
[0511] [Table 4]
[0512]
[0513] A mixture of rod-shaped liquid crystals [a mixture of the following liquid crystal compounds (RA) (RB) (RC) in a ratio of 84:14:2 (mass ratio), average molar absorption coefficient at a wavelength of 300 to 400 nm: 140 / mol·cm]
[0514] [Chemical formula 27]
[0515]
[0516] Chiral Reagent A
[0517] [Chemical formula 28]
[0518]
[0519] Surfactant F2
[0520] [Chemical formula 29]
[0521]
[0522] Surfactant F3
[0523] [Chemical formula 30]
[0524]
[0525] Photopolymerization initiator B
[0526] [Chemical formula 31]
[0527]
[0528] Chiral reagent A is a chiral reagent whose helical twisting power (HTP: Helical Twisting Power) decreases due to light.
[0529] (Reflective layer coating liquid D-1)
[0530] The composition shown below was stirred and dissolved in a container maintained at a temperature of 50° C. to prepare a circularly polarized light reflecting layer coating liquid D-1.
[0531]
[0532] (Reflective layer coating liquid D-2)
[0533] Reflective layer coating liquid D-2 was prepared in the same manner as in the reflective layer coating liquid D-1, except that the addition amount of the chiral agent A was changed as shown in Table 5 below.
[0534] [Table 5]
[0535]
[0536] Discotic liquid crystal (A)
[0537] [Chemical formula 32]
[0538]
[0539] Discotic liquid crystal (B)
[0540] [Chemical formula 33]
[0541]
[0542] Polymerizable monomer EM1
[0543] [Chemical formula 34]
[0544]
[0545] Surfactant F4 (weight average molecular weight: 15000)
[0546] [Chemical formula 35]
[0547]
[0548] [Manufacturing of reflective circular polarizer 1]
[0549] As a pseudo support, a PET (polyethylene terephthalate) film (A4100 manufactured by TOYOBO CO., LTD.) having a thickness of 50 μm was prepared. The PET film had an easy-adhesion layer on one side.
[0550] The surface without the easy-adhesive layer of the PET film was rubbed, and the reflective layer coating liquid R-1 prepared above was applied using a wire bar coater, and then dried at 110°C for 120 seconds. Then, the surface was irradiated at 100°C with an illumination of 80 mW / cm in a low oxygen atmosphere (less than 100 ppm). 2 、Irradiation 500mJ / cm 2 The coating was cured by light from a metal halide lamp, thereby forming a red light reflecting layer composed of a cholesteric liquid crystal layer. The light irradiation was performed from the cholesteric liquid crystal layer side. At this time, the coating thickness was adjusted so that the film thickness of the red light reflecting layer after curing became 4.5 μm.
[0551] Next, the discharge rate was 150W·min / m 2 After the red light reflecting layer was subjected to corona treatment, the reflective layer coating liquid D-1 was applied to the corona treated surface using a wire bar coater. Next, the coating film was dried at 70°C for 2 minutes to vaporize the solvent, and then heated and aged at 115°C for 3 minutes to obtain a uniform orientation state. Then, the coating film was maintained at 45°C and irradiated with ultraviolet rays (300 mJ / cm 2 ) to cure, thereby forming a yellow light reflecting layer on the red light reflecting layer. The light irradiation was performed from the cholesteric liquid crystal layer side. At this time, the coating thickness was adjusted so that the film thickness of the yellow light reflecting layer after curing became 3.3 μm.
[0552] Next, the yellow light reflecting layer was coated with the reflective layer coating liquid R-2 using a wire bar coater and dried at 110°C for 120 seconds. Then, the yellow light reflecting layer was irradiated at 100°C with an illumination of 80 mW and an irradiation amount of 500 mJ / cm in a low oxygen atmosphere (less than 100 ppm). 2 The green light reflecting layer was formed on the yellow light reflecting layer by curing with the light of a metal halide lamp. The light irradiation was performed from the cholesteric liquid crystal layer side. At this time, the coating thickness was adjusted so that the film thickness of the green light reflecting layer after curing became 2.7 μm.
[0553] Next, the discharge rate was 150W·min / m 2 After the green light reflecting layer was subjected to corona treatment, the reflecting layer coating liquid D-2 was applied to the corona treated surface using a wire bar coater. Next, the coating film was dried at 70°C for 2 minutes to vaporize the solvent, and then heated and aged at 115°C for 3 minutes to obtain a uniform orientation state. Then, the coating film was maintained at 45°C and irradiated with ultraviolet rays (300 mJ / cm 2 ) to cure, thereby forming a blue light reflecting layer on the green light reflecting layer. The light irradiation was performed from the cholesteric liquid crystal layer side. At this time, the coating thickness was adjusted so that the film thickness of the blue light reflecting layer after curing became 2.5 μm.
[0554] In this way, the reflective circular polarizer 1 was manufactured.
[0555] 〔Production of optical lenses〕
[0556] An adhesive sheet "NCF-D692 (5)" manufactured by LINTEC Corporation was attached to the blue light reflection layer side of the reflective circular polarizer 1. With the separator of the adhesive sheet peeled off, the reflective circular polarizer 1 was vacuum-formed into a concave surface along a plano-concave lens (made of optical glass) with a diameter of 50 mm and a radius of curvature of 90 mm, with the blue light reflection layer side in contact with the plano-concave lens, with reference to Japanese Patent Publication No. 2012-116094. Then, the PET substrate of the reflective circular polarizer 1 was peeled off from the lens to obtain a lens with a reflective circular polarizer.
[0557] Next, in the same manner as above, the phase difference side of the optically anisotropic film 1 with a laminated film of Example 1 (phase difference layer 1 / photo-alignment layer / light-absorbing anisotropic layer / adhesive layer / laminated film) was overlapped and molded with the reflective circular polarizer 1. In this way, an optical lens 1 having lens / reflective circular polarizer 1 / adhesive layer / phase difference layer 1 / photo-alignment layer / light-absorbing anisotropic layer laminated in this order was produced.
[0558] [Production of virtual reality display device]
[0559] The virtual reality display device "VIVE FLOW" manufactured by HTC was disassembled and the optical lens was taken out. In addition, "VIVE FLOW" is a virtual reality display device that uses a cookie lens, and as an image display device, a liquid crystal display device that emits circularly polarized light through a polarizing plate attached to the surface is used.
[0560] The optical lenses taken out were two: a biconvex lens having a half mirror coating formed on one surface and a plano-convex lens having an optical layer laminated on a flat surface.
[0561] Remove the plano-convex lens and set the optical lens 1 so that the plane side becomes the biconvex lens side. At this time, in order to properly display the virtual reality display image, the optical lens 1 is set while adjusting the distance from the biconvex lens.
[0562] In this manner, a virtual reality display device 1 using the molded body 1 of Example 1 was produced.
[0563] Furthermore, virtual reality display devices 2 to 5 and H1 were produced by the same method as above except that the molded body 1 was changed to molded bodies 2 to 5 and H1.
[0564] [evaluate]
[0565] In each virtual reality display device produced, a black and white checkered pattern was displayed on the image display device, and the degree of light leakage was visually evaluated according to the following 4 levels. The results are shown in the following Table 6. In addition, if there is light leakage, a double image can be visually recognized, and the contrast of the corresponding part will be reduced.
[0566] A: No double image at all
[0567] B: Slightly visible double images, but no problem
[0568] C: Double images are visible, but there is no practical problem
[0569] D: Ghosting is clearly visible
[0570] [Table 6]
[0571]
[0572] The results shown in Table 6 show that when a laminated body in which the variation in the film thickness of the alignment film is 10% or less is used, light leakage is reduced and display performance becomes good (molded bodies 1 to 5 of Examples 1 to 5).
[0573] (Fourth embodiment of virtual reality display device)
[0574] [Example 7]
[0575] [Fabrication of Circular Polarizer]
[0576] For the laminate 3 fabricated in Example 3, on the light absorption anisotropic layer side of the laminate 3, a retardation layer 1 was bonded using an adhesive sheet "NCF-D692(5)" manufactured by LINTECCorporation., and a circular polarizer 7 having a structure of an alignment film / light absorption anisotropic layer / adhesive layer / retardation layer 1 was fabricated. The film thickness of the adhesive layer was 5 μm, and the oxygen permeability coefficient exceeded 200 cc / m 2 ·day·atm.
[0577] [Fabrication of Virtual Reality Display Device]
[0578] The virtual reality display device "Meta Quest Pro" manufactured by Meta Platforms, Inc. was disassembled, and the optical lens was taken out. In addition, "Meta Quest Pro" is a virtual reality display device using a pancake lens, and as an image display device, a liquid crystal display device that emits circularly polarized light through a polarizer attached to the surface was used.
[0579] Moreover, the taken-out optical lens was two convex-planar lenses 1 with a half-mirror coating on the convex surface and a retardation film and an antireflection film attached on the plane, and convex-planar lenses 2 with an optical laminate (reflective linear polarizer / glass / absorptive linear polarizer / retardation / lens) attached on the plane side and an antireflection film attached on the convex surface side.
[0580] The absorptive linear polarizer / retardation of the above convex-planar lens 2 was removed, and the circular polarizer 7 fabricated above was replaced by aligning the transmission axes with each other in such a way that the light absorption anisotropic layer side became the reflective linear polarizer side. At this time, the convex-planar lens 1 was set while adjusting the distance from the convex-planar lens 2 so that a virtual reality display image was appropriately displayed, thereby constructing the virtual reality display device 7 of Example 7.
[0581] [Example 8]
[0582] [Preparation of UV Adhesive 1]
[0583] UV Adhesive 1 having the following composition was prepared.
[0584]
[0585] CPI-100P
[0586] [Chemical Formula 36]
[0587]
[0588] The adhesive layer of the circular polarizing plate 7 was changed to a UV adhesive layer composed of the above-mentioned UV adhesive 1, and it was exposed to light with an illuminance of 1000 mJ for curing. Except for this, the virtual reality display device 8 of Example 8 was produced in the same manner as in Example 7. The oxygen permeability coefficient of the UV adhesive layer is 200 cc / m 2 ·day·atm or less.
[0589] [Example 9]
[0590] [Preparation of PVA Adhesive 1]
[0591] PVA adhesive 1 having the following composition was prepared.
[0592] With respect to 100 parts by mass of a polyvinyl alcohol-based resin containing acetoacetyl groups (average degree of polymerization: 1200, saponification degree: 98.5 mol%, acetoacetylation degree: 5 mol%), 20 parts by mass of hydroxymethylmelamine was dissolved in pure water at a temperature of 30°C to prepare an aqueous solution (PVA adhesive 1) adjusted to a solid content concentration of 3.7%.
[0593] Except for changing the adhesive layer of the circular polarizing plate 7 to a PVA adhesive layer composed of the above-mentioned PVA adhesive 1, the virtual reality display device 9 of Example 9 was produced in the same manner as in Example 7. The film thickness of the PVA adhesive layer is 1 μm, and the oxygen permeability coefficient is 200 cc / m 2 ·day·atm or less.
[0594] [Example 10]
[0595] Using a polycarbonate film with an inverse dispersion retardation obtained by polymer stretching (manufactured by TEIJIN LIMITED., trade name: PURE-ACE RM Re(550)=147 nm) instead of the retardation film 1 cured with liquid crystal in Example 9, the virtual reality display device 10 of Example 10 was produced.
[0596] [Evaluation]
[0597] In each of the produced virtual reality display devices, the above-mentioned distortion evaluation and durability evaluation of the VR image were performed.
[0598] [Table 7]
[0599]
[0600] From the results shown in Table 7 above, it can be seen that when using a laminate with a film thickness variation of the alignment film of 10% or less, the display performance becomes good (Examples 7 to 10). And it can be seen that even in a structure without a protective layer, when using an oxygen permeability coefficient of 200 cc / m 2The adhesive layer is bonded at a strength of less than ·day·atm and has excellent durability.
[0601] Explanation of symbols
[0602] 100-virtual reality display device, 11-first phase difference layer, 12-second phase difference layer, 13-third phase difference layer, 21-first absorption type linear polarizer, 22-second absorption type linear polarizer, 30-reflection type circular polarizer, 40-half-reflecting mirror, 50-anti-reflection layer, 60-positive C plate, 70-image display panel.
Claims
1. A laminate comprising an alignment film and a light absorption anisotropic layer disposed on the alignment film, wherein: The light absorption anisotropic layer contains a liquid crystal compound and a dichroic substance. The film thickness variation of the alignment film is 10% or less.
2. The laminate according to claim 1, wherein The dichroic substance contains a dichroic azo dye compound having a thienothiazole skeleton.
3. The laminate according to claim 1, wherein The content of the dichroic substance contained in the light absorption anisotropic layer is 40 to 250 mg / cm 3 .
4. The laminate according to claim 1, wherein The alignment film contains a polymer compound, When the secondary ion intensity originating from the polymer compound in the oriented film is measured using time-of-flight secondary ion mass spectrometry while irradiating an ion beam from the surface of the oriented film on the side of the light absorption anisotropic layer toward the surface on the opposite side of the light absorption anisotropic layer, the maximum value of the secondary ion intensity originating from the polymer compound exists in the region from the surface on the side opposite to the light absorption anisotropic layer to a thickness position of 100 nm.
5. The laminate according to claim 4, wherein The polymer compound has a repeating unit represented by the following formula (2): In the formula (2), R 2 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, L 2 represents a single bond or a divalent linking group, R 3 It represents an aliphatic hydrocarbon group which may have a substituent, or a group in which one or more -CH2- constituting the aliphatic hydrocarbon group are substituted by -O-, -S-, -NH-, -N(Q)- or -CO-, and Q represents a substituent.
6. The laminate according to claim 1, wherein A protective layer is provided on the side of the light absorption anisotropic layer opposite to the alignment film, The oxygen permeability coefficient of the protective layer is 200cc / m 2 ·day·atm or less.
7. The laminate according to claim 6, wherein: The protective layer is composed of a polyvinyl alcohol-based resin film.
8. The laminate according to claim 1, wherein The laminated body includes the alignment film, the light absorption anisotropic layer, a tackiness adhesive layer, and a phase difference layer adjacent to each other in this order.
9. The laminate according to claim 8, wherein The oxygen coefficient of the adhesive layer is 200cc / m 2 ·day·atm or less.
10. The laminate according to claim 1, wherein The stacked body has a curved shape.
11. A method for producing a laminated body, which is a method for producing the laminated body according to any one of claims 1 to 10, the method for producing a laminated body comprising: an alignment film forming step of forming an alignment film on a substrate using an alignment film forming composition; a light absorption anisotropic layer forming step of forming a light absorption anisotropic layer on the alignment film using a light absorption anisotropic layer forming composition containing a liquid crystal compound and a dichroic substance after the alignment film forming step; and The substrate peeling step is to peel off the substrate after the light absorption anisotropic layer forming step to produce a laminate of the alignment film and the light absorption anisotropic layer.
12. The method for producing a laminate according to claim 11, wherein: The alignment film forming composition contains a polymer compound. The absolute value of the difference between the SP value of the polymer compound and the SP value of the substrate is 1.7 MPa 1 / 2 the following.
13. The method for producing a laminate according to claim 11, wherein: The composition for forming an alignment film has a viscosity at 25° C. of 2 mPa·s or more and less than 10 mPa·s.
14. The method for producing a laminate according to claim 11, wherein: The alignment film forming step includes a drying process of drying the coating film having a solid content concentration of 60% or less by using wind at a wind speed of 2 m or less after applying the alignment film forming composition on the substrate.
15. A virtual reality display device, comprising an image display panel, a first absorption type linear polarizer, a first phase difference layer, a reflection type circular polarizer, a half mirror, a second phase difference layer and a second absorption type linear polarizer in sequence, The second absorbing linear polarizer is the laminated body according to any one of claims 1 to 10.
Citation Information
Patent Citations
Chitsupukondensanoseizohoho
JP1982053922A
Optical pickup device
JP1984060743A
Liquid crystal display surface lighting apparatus
JP1987059925A
Light-absorbing anisotropic thin film and manufacture thereof
JP1999305036A
Anisotropic film and liquid crystal display device
JP2001133630A